Superabsorbent polymer
Patent Information
- Application Number
- CN202580020508.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-01-30
- Filing Date
- 2025-03-20
- Publication Date
- 2026-10-13
AI Technical Summary
[0007]然而,存在以下缺点:超吸收性聚合物的整体物理特性例如表面张力、渗透性、体积密度等由于使用发泡剂而劣化,并且产生的细粉末的量增加,并因此,持续需要开发能够在不使用发泡剂的情况下改善超吸收性聚合物的吸收特性的技术
[0026]根据本公开的超吸收性聚合物,通过将表示离心保留容量(CRC)、横纵比(A/R)、凸度和圆形度之间关系的因子值F1和F2调节至预定值,可以提供在相应聚合物应用于实际产品时能够实现优异品质的超吸收性聚合物。
Smart Images

Figure CN122910263A_ABST
Abstract
Description
Technical Field
[0001] Cross-references to related applications
[0002] This application claims priority to Korean Patent Application No. 10-2024-0038728, filed March 20, 2024, and U.S. Patent Application No. 19 / 041,418, filed January 30, 2025, the contents of which are incorporated herein by reference in their entirety.
[0003] This disclosure relates to superabsorbent polymers. More specifically, this disclosure relates to superabsorbent polymers that exhibit improved absorption rates and absorption performance. Background Technology
[0004] Super absorbent polymers (SAPs) are synthetic polymer materials capable of absorbing 500 to 1,000 times their own weight in water. They are known by various names, such as super absorbency material (SAM) and absorbent gel material (AGM). SAPs were first used in diapers and hygiene products, and are now widely used in materials for: horticultural soil conditioners, waterproofing materials in civil engineering and construction, seedling sheets, and preservatives and dressings in the food distribution industry.
[0005] Superabsorbent polymers are widely used in hygiene products such as diapers or sanitary napkins. In hygiene products, superabsorbent polymers are typically contained in pulp in a dispersed state. However, in recent years, efforts have been made to provide hygiene products such as thinner diapers, and as part of these efforts, there is active development of products with reduced or even no pulp content, such as so-called pulp-free diapers.
[0006] As mentioned above, in the case of hygiene products with reduced or no pulp content, superabsorbent polymers are included in a relatively high proportion, making it inevitable that superabsorbent polymer particles are contained in multiple layers of the hygiene product. For all the superabsorbent polymer particles contained in multiple layers to more effectively absorb large amounts of liquid, such as urine, the superabsorbent polymer needs to exhibit not only high absorbency but also a rapid vortex time. Meanwhile, the most common method for improving these absorbency properties is to form a porous structure within the superabsorbent polymer, thereby increasing the surface area of the superabsorbent polymer. To increase the surface area of the superabsorbent polymer, a method is typically employed that forms a porous structure within the base polymer powder by including a foaming agent in the monomer composition and performing crosslinking polymerization.
[0007] However, the following drawbacks exist: the overall physical properties of superabsorbent polymers, such as surface tension, permeability, and bulk density, are degraded due to the use of foaming agents, and the amount of fine powder generated increases. Therefore, there is a continuous need to develop technologies that can improve the absorption properties of superabsorbent polymers without the use of foaming agents.
[0008] Therefore, in order to fundamentally solve the above problems, there is a continued need to develop technologies that can produce superabsorbent polymers without generating fine powder. Summary of the Invention
[0009] Technical issues
[0010] This disclosure aims to provide superabsorbent polymers that achieve excellent quality when applied to actual products by determining the relationship between the absorption characteristics of superabsorbent polymers and their particle shape, thereby adjusting the factor values F1 and F2, which represent the relationship between centrifugal retention capacity (CRC), aspect ratio (A / R), convexity, and roundness, to predetermined values, thereby improving the absorption rate and absorption performance.
[0011] Technical solution
[0012] According to one exemplary aspect of this disclosure
[0013] Superabsorbent polymers are provided.
[0014] It is a superabsorbent polymer based on polyacrylic acid (salt).
[0015] The F1 calculated using Equation 1 is between 0.55 and 0.65, and
[0016] The F² calculated using Equation 2 is between 0.65 and 0.75:
[0017] [Equation 1]
[0018] F1 = K1×[{(A 0.1 ×C×D 0.5 )} / (B 0.3 )]
[0019] [Equation 2]
[0020] F2 = K2×[(B 0.2 ) / {(A 0.1 ×C×D 0.5 )}]
[0021] In equations 1 and 2 above,
[0022] i) K1 and K2 are correction constants of 0.5 and 0.8, respectively.
[0023] ii) A represents the centrifugation retention capacity (CRC) of particles with diameters ranging from 300 μm to 425 μm, measured according to the WSP 241.3 method of the EDANA method, and
[0024] iii) B, C and D are the average aspect ratio (A / R), average convexity and average roundness of particles with a diameter of 100 μm to 600 μm, respectively.
[0025] Beneficial effects
[0026] According to the superabsorbent polymer disclosed herein, by adjusting the factor values F1 and F2, which represent the relationship between centrifugal retention capacity (CRC), aspect ratio (A / R), convexity, and roundness, to predetermined values, a superabsorbent polymer that can achieve excellent quality when the corresponding polymer is applied to an actual product can be provided.
[0027] In particular, superabsorbent polymers with an excellent balance of physical properties can be provided by improving absorption performance, such as centrifugal retention capacity and absorption rate under pressure, while simultaneously improving vortex time.
[0028] Furthermore, when the aforementioned superabsorbent polymers are applied to hygiene products such as diapers, the superabsorbent polymers can absorb excreted bodily fluids at a high speed and in a relatively large amount, thus preventing problems such as the accumulation of bodily fluids inside the hygiene product or their leakage to the outside.
[0029] That is, it is possible to provide superabsorbent polymers that can rapidly absorb bodily fluids and retain large amounts of bodily fluids when applied to products without allowing them to leak to the outside. Attached Figure Description
[0030] Figure 1 The sample dispersion unit settings in Malvern Panalytical Co., Ltd.'s morphologi 4 are shown.
[0031] Figure 2 The illumination settings for the Malvern Panalytical Co., Ltd. morphologi 4 are shown.
[0032] Figure 3 The Optics Selection settings in Malvern Panalytical Co., Ltd.'s morphologi 4 are shown.
[0033] Figure 4The scan area settings are shown in Malvern Panalytical Co., Ltd.'s morphologi 4.
[0034] Figure 5 This is a graph showing the correlation between factor value F1 and vortex time; and
[0035] Figure 6 This is a graph showing the correlation between the factor value F2 and the 1-minute absorption rate in water with a conductivity of 110 μS / cm. Detailed Implementation
[0036] According to one example of this disclosure, a superabsorbent polymer is provided, which is a polyacrylic acid (salt) based superabsorbent polymer, wherein F1 calculated by Equation 1 below is 0.55 to 0.65, and F2 calculated by Equation 2 below is 0.65 to 0.75:
[0037] [Equation 1]
[0038] F1 = K1(0.5)×[{(A(CRC) 0.1 ×C (convexity) ×D (circularity) 0.5 )} / (B(Aspect Ratio) 0.3 )]
[0039] [Equation 2]
[0040] F2 = K2×[(B 0.2 ) / {(A 0.1 ×C×D 0.5 )}]
[0041] In equations 1 and 2 above,
[0042] i) K1 and K2 are correction constants of 0.5 and 0.8, respectively.
[0043] ii) A represents the centrifugation retention capacity (CRC) of particles with diameters ranging from 300 μm to 425 μm, measured according to the WSP 241.3 method of the EDANA method, and
[0044] iii) B, C and D are the average aspect ratio (A / R), average convexity and average roundness of particles with a diameter of 100 μm to 600 μm, respectively.
[0045] Invention Embodiments
[0046] Unless otherwise defined herein, all technical and scientific terms are used for descriptive purposes only and are not intended to limit this disclosure. Unless the context clearly indicates otherwise, singular expressions include plural expressions. In this disclosure, it should be understood that the terms “comprising,” “including,” or “having” are intended to specify the presence of the stated features, numbers, steps, elements, or combinations thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements, or combinations thereof.
[0047] This disclosure can be modified in a variety of ways and can take many forms, and specific aspects are illustrated and described in detail below. However, it should be understood that this is not intended to limit this disclosure to the specific forms disclosed, but rather to cover all modifications, equivalents, and alternatives that fall within the spirit and scope of the above-described concepts and techniques.
[0048] The terminology used herein is for reference only to specific embodiments and is not intended to limit this disclosure. Furthermore, unless the phrase clearly indicates the opposite meaning, the singular form used herein includes the plural form.
[0049] As used in this disclosure, the term "polymer" means a water-soluble olefinic unsaturated monomer in a polymerized state and may cover any range of water content or particle size.
[0050] Furthermore, depending on the context, the term "superabsorbent polymer" means a cross-linked polymer or a base polymer in powder form made from pulverized superabsorbent polymer particles, or is used to cover cross-linked polymers or base polymers that have undergone additional processing (e.g., drying, pulverizing, grading, surface cross-linking, etc.) to be in a commercially viable state.
[0051] Furthermore, the term "fine powder" refers to particles with a diameter of less than 150 μm in the superabsorbent polymer granules. The particle size of these polymer particles can be measured according to the EDANA WSP 220.3 method, a standard of the European Disposables and Nonwovens Association (EDANA).
[0052] In addition, the term "shredding" refers to cutting hydrogel polymers into small fragments of millimeters to improve drying efficiency, and is used to distinguish it from pulverizing them to the micron or typical particle level.
[0053] In addition, the term "micronizing / micronization" refers to pulverizing hydrogel polymers into fragments with a particle size of tens to hundreds of micrometers, and is used to distinguish it from "shredding".
[0054] The superabsorbent polymer and its preparation method according to a particular aspect of this disclosure will be described in more detail below.
[0055] I. Superabsorbent polymers based on polyacrylic acid (salt)
[0056] Hydrogel-phase polymers obtained through the polymerization of acrylic acid-based monomers are commercially available as powder-phase superabsorbent polymers after undergoing processes such as drying, grinding, grading, and surface crosslinking. In recent years, continuous efforts have been made to provide superabsorbent polymers exhibiting further improved absorption rates.
[0057] The most common method for increasing the absorption rate is to form a porous structure inside the superabsorbent polymer to increase its surface area. In order to increase the surface area of the superabsorbent polymer, a method is usually adopted to form a porous structure inside the base polymer powder by including a foaming agent in the monomer composition and carrying out crosslinking polymerization.
[0058] However, commonly used methods are difficult to create sufficient surface area, which leads to the following problem: unabsorbed bodily fluids flow inside the sanitary product or leak to the outside during actual urination, causing discomfort to the user.
[0059] Therefore, the inventors continued to study ways to improve both absorption rate and absorption performance, and as a result, they found that the centrifugal retention capacity (CRC), which represents the absorption characteristics of superabsorbent polymer particles, is closely related to the aspect ratio (A / R), convexity, and roundness, which represent the shape of superabsorbent polymer particles.
[0060] Specifically, the inventors determined through experiments that if the factor values F1 and F2, which represent the relationship between centrifugal retention capacity (CRC), aspect ratio (A / R), convexity, and roundness, are adjusted to predetermined values, the absorption rate can be improved while the absorption performance, such as centrifugal retention capacity and absorption rate under pressure, can be improved, thereby achieving excellent quality when the corresponding polymer is applied to actual products, and thus the present disclosure was completed.
[0061] According to one exemplary aspect of this disclosure
[0062] Superabsorbent polymers are provided.
[0063] It is a superabsorbent polymer based on polyacrylic acid (salt).
[0064] The F1 calculated using Equation 1 is between 0.55 and 0.65, and
[0065] The F² calculated using Equation 2 is between 0.65 and 0.75:
[0066] [Equation 1]
[0067] F1 = K1×[{(A 0.1 ×C×D 0.5 )} / (B 0.3 )]
[0068] [Equation 2]
[0069] F2 = K2×[(B 0.2 ) / {(A 0.1 ×C×D 0.5 )}]
[0070] In equations 1 and 2 above,
[0071] i) K1 and K2 are correction constants of 0.5 and 0.8, respectively.
[0072] ii) A represents the centrifugation retention capacity (CRC) of particles with diameters ranging from 300 μm to 425 μm, measured according to the WSP 241.3 method of the EDANA method, and
[0073] iii) B, C and D are the average aspect ratio (A / R), average convexity and average roundness of particles with a diameter of 100 μm to 600 μm, respectively.
[0074] As described above, the inventors determined that there is a correlation between the absorption properties of superabsorbent polymers and their particle shape. They then prepared absorbent polymers with a variety of particle shapes to measure the values of various shape-related factors (aspect ratio, convexity, and roundness) and the values of factors related to absorption properties (CRC, vortex, and 110 μS / cm 1-minute absorption rate), and determined that these values have a specific correlation.
[0075] That is, it was determined that the factor value F1 of Equation 1 above is proportional to the vortex time, and the factor value F2 of Equation 2 above is proportional to the 1-minute absorption rate in water with a conductivity of 110 μS / cm.
[0076] Therefore, if the factor values F1 and F2 of Equations 1 and 2 above are adjusted to a specific range, a superabsorbent polymer with an excellent balance of physical properties can be achieved by improving the absorption rate and absorption performance at the same time.
[0077] Specifically, the factor value F1 of Equation 1 above for the superabsorbent polymer of this disclosure can be 0.55 or greater, 0.56 or greater, 0.57 or greater, or 0.58 or greater, and 0.65 or less, 0.64 or less, 0.63 or less, 0.62 or less, or 0.61 or less.
[0078] If the F1 value meets the above range, the pore structure in the superabsorbent polymer particles can be well-developed or the specific surface area of the particles can be increased, so that the superabsorbent polymer can have an excellent absorption rate. However, if the above range is not met, the surface of the final diaper may become damp or leak.
[0079] Furthermore, the factor value F2 of Equation 2 above for the superabsorbent polymer of this disclosure can be 0.65 or greater, 0.66 or greater, 0.67 or greater, or 0.68 or greater, and 0.75 or less, 0.74 or less, 0.73 or less, 0.72 or less, or 0.71 or less.
[0080] If the F2 value meets the above range, the initial absorption characteristics are excellent, and the surface of the diaper can feel soft, smooth, and dry. However, if the value does not meet the above range, there may be an increase in cost due to the increased amount of superabsorbent polymer used in the diaper absorbent core.
[0081] In Equations 1 and 2 above, centrifugal retention capacity (CRC) refers to the absorption rate of the superabsorbent polymer under no-load conditions, and the larger the value, the better the absorption performance of the superabsorbent polymer.
[0082] Specifically, the centrifugal retention capacity (CRC) of the superabsorbent polymer of this disclosure, measured according to the EDANA WSP 241.3 method, for particles with a diameter of 300 μm to 425 μm, can be in the following ranges: 30 g / g or greater, 31 g / g or greater, or 32 g / g or greater, and 50 g / g or less, 45 g / g or less, or 40 g / g or less.
[0083] Centrifugal retention capacity (CRC) can be measured according to the EDANA WSP 241.3 method of the European Disposable Goods and Nonwovens Association (EDANA), and the specific measurement method will be described in more detail in the following experimental examples.
[0084] Meanwhile, the aspect ratio (A / R) is a parameter that can determine the symmetry of particles, and it refers to the ratio of the shortest diameter of a particle to its longest diameter.
[0085] The aspect ratio has values from 0 to 1, where the aspect ratio is 1 if all axes are symmetrical to each other (as in a perfect sphere or cube), and the closer the aspect ratio is to 1, the closer the particle shape is to symmetry, and the closer the aspect ratio is to 0, the closer the particle shape is to asymmetry.
[0086] Specifically, the average aspect ratio (A / R) of the superabsorbent polymer of this disclosure with a particle size of 100 μm to 600 μm can be 0.65 or greater, 0.67 or greater, 0.69 or greater, 0.70 or greater, 0.71 or greater, or 0.72 or greater, and 0.85 or less, 0.84 or less, 0.83 or less, 0.82 or less, 0.81 or less, or 0.80 or less.
[0087] It can be seen that the smaller the average aspect ratio, the larger the specific surface area due to the increase in particle asymmetry. However, when only the specific surface area is increased, there may be problems such as deterioration of absorption performance, such as centrifugal retention capacity and absorption rate under pressure.
[0088] Therefore, in order to simultaneously improve absorption rate and absorption performance to achieve an excellent balance of properties, the average aspect ratio of particles with a particle size of 100 μm to 600 μm can be, for example, 0.65 to 0.85.
[0089] Meanwhile, convexity is a parameter used to measure particle profile and particle surface roughness, and is calculated by the following Equation 3.
[0090] [Equation 3]
[0091] Convexity = convex hull perimeter / actual particle perimeter
[0092] In equation 3 above,
[0093] The convex hull perimeter refers to the length of an elastic band that is assumed to be bounded by an imaginary elastic band stretched around the contour of a 2D image captured as a 3D particle to be measured.
[0094] Actual particle perimeter refers to the actual perimeter of the image captured as a 2D image of the 3D particle to be measured.
[0095] The convexity value ranges from 0 to 1, and it can be seen that the closer the convexity is to 1, the smoother the particle profile, and the closer the convexity is to 0, the rougher or less smooth the particle profile.
[0096] Specifically, the average convexity of the superabsorbent polymer of the present disclosure with particles having a particle size of 100 μm to 600 μm can be 0.80 or greater, 0.82 or greater, 0.84 or greater, or 0.86 or greater, and 0.94 or less, 0.92 or less, or 0.90 or less.
[0097] It can be seen that the smaller the average convexity, the larger the specific surface area. However, when only the specific surface area is increased, the following problems may occur when mixing superabsorbent polymer particles and surface crosslinking agents: the absorption rate under pressure decreases due to uneven coating, or the absorption performance, such as centrifugal retention capacity and absorption rate under pressure, deteriorates due to the increased amount of surface crosslinking agent added to improve coating efficiency.
[0098] Therefore, in order to simultaneously improve absorption rate and absorption performance to achieve an excellent balance of properties, the average convexity of particles with a particle size of 100 μm to 600 μm can be, for example, 0.80 to 0.94.
[0099] Meanwhile, roundness is a parameter that can determine how close the superabsorbent polymer particles are to perfect spheres, and it is calculated by the following Equation 4.
[0100] [Equation 4]
[0101] Roundness = CE particle perimeter / actual particle perimeter
[0102] In equation 4 above,
[0103] The CE particle perimeter refers to the perimeter of an equivalent circle having the same area as the image captured as a 2D image of the 3D particle to be measured.
[0104] Actual particle perimeter refers to the actual perimeter of the image captured as a 2D image of the 3D particle to be measured.
[0105] The roundness value ranges from 0 to 1, where the roundness of a perfect sphere is 1. It can be seen that the closer the roundness is to 1, the closer the particle is to a perfect sphere, and the closer the roundness is to 0, the more sharp the shape of the particle is, such as a very narrow rod shape.
[0106] Specifically, the average sphericity of the superabsorbent polymer particles with a particle size of 100 μm to 600 μm can be 0.70 or greater, 0.71 or greater, 0.72 or greater, 0.73 or greater, or 0.74 or greater, and 0.90 or less, 0.88 or less, 0.86 or less, 0.84 or less, or 0.82 or less.
[0107] It can be seen that the smaller the average sphericity, that is, the more the particles deviate from perfect spheres and have a very sharp shape, the larger the specific surface area. However, when only the specific surface area is increased, there may be problems with absorption performance such as centrifugal retention capacity and absorption rate under pressure.
[0108] Therefore, in order to simultaneously improve absorption rate and absorption performance to achieve an excellent balance of properties, the average sphericity of particles with a particle size of 100 μm to 600 μm can be, for example, 0.70 to 0.90.
[0109] The average aspect ratio, average convexity, and average roundness were obtained by averaging the values by randomly dispersing particles on a stage under vacuum in a measuring device, and then ensuring that n was 200 or greater.
[0110] Furthermore, aspect ratio, convexity, and roundness are similar in that the shape of superabsorbent polymer particles is quantified through them, but each has a different meaning.
[0111] That is, if the shape of the particles changes, the aspect ratio, convexity, and roundness values may all change, or only some of them may change.
[0112] The aforementioned aspect ratio, convexity, and roundness can be measured using a variety of commercial devices that quantify and analyze particle morphology using particle-based image analysis. For example, these parameters can be measured using the Malvern Panalytical Co., Ltd. morphologi 4, and specifically, can be measured through the following four steps, which will be described in more detail in the experimental examples below.
[0113] 1) Sample preparation: Prepare the superabsorbent polymer particles to be measured. If the aspect ratio, convexity, and roundness of particles with a specific particle size range are to be measured, the sample is prepared by classifying the particles with the specific particle size for 10 minutes at an amplitude of 1.0 using a Retsch classifier.
[0114] At this point, the particle size of the superabsorbent polymer particles can be measured according to the EDANA WSP 220.3 method, a standard of the European Disposable Goods and Nonwovens Association (EDANA).
[0115] 2) Image acquisition: Place the prepared sample on the stage in the instrument, and then scan it at 2.5x magnification to obtain images of each particle.
[0116] 3) Image processing: For the acquired images, the parameters of each particle are measured by capturing the 2D images of the 3D particles, such as the equivalent circle (CE) diameter, the shortest diameter, the longest diameter, and the actual particle circumference.
[0117] 4) Based on the data from the analysis of each particle, a distribution map of the parameters of all particles contained in the sample is obtained.
[0118] Meanwhile, the average diameter of the equivalent circle (CE) of the superabsorbent polymer can be between 350 μm and 490 μm.
[0119] The CE diameter can refer to the diameter of a circle having the same area as the image obtained by capturing a 3D image of a particle as a 2D image, and the size of a particle can be represented by the CE diameter.
[0120] However, since particles with different shapes may have the same CE diameter value, the shape of a particle can be represented by the particle's roundness and aspect ratio along with the CE diameter.
[0121] The average CE diameter of the superabsorbent polymer can be 350 μm or larger, 370 μm or larger, or 390 μm or larger, or 490 μm or smaller, 480 μm or smaller, or 470 μm or smaller.
[0122] Superabsorbent polymers exhibit varying trends in absorption characteristics and absorption rates depending on their particle size. Larger particle sizes generally result in greater water-holding capacity but longer absorption times, while smaller particle sizes lead to faster absorption but less water-holding capacity. Therefore, a suitable particle size distribution is necessary, and when the superabsorbent polymer possesses the particle size specified in this disclosure, it achieves an excellent balance between absorption capacity and absorption rate.
[0123] Furthermore, the superabsorbent polymer prepared according to one aspect of this disclosure can have a uniform particle size distribution, and thus can provide a superabsorbent polymer with excellent overall absorption properties such as centrifugal retention capacity and absorption rate under pressure, as well as excellent rewetting properties, and particularly excellent physical properties of initial absorption ratio.
[0124] The superabsorbent polymer according to one aspect of this disclosure can have a high absorption rate and a low fine powder content, and can have a centrifugal retention capacity (CRC) and absorbance under pressure (AUP) equal to or higher than those of superabsorbent polymers prepared by conventional methods (these are overall absorption characteristics).
[0125] Furthermore, due to the low content of extractable contents (EC), it can provide a superabsorbent polymer with excellent permeability and rewetting properties.
[0126] The vortex time of the superabsorbent polymer disclosed herein, measured at 24.0 °C according to the vortex measurement method, for particles with a particle size of 300 μm to 425 μm, can be 40 seconds or less.
[0127] More specifically, the vortex time can be 40 seconds or less, 35 seconds or less, 33 seconds or less, or 30 seconds or less. Furthermore, the smaller the value, the better the vortex time, and although the lower limit of the vortex time is theoretically 0 seconds, it can be, for example, 10 seconds or more, 15 seconds or more, or 20 seconds or more.
[0128] In this case, the method for measuring the vortex time of the superabsorbent polymer will be described in more detail in the experimental examples described later.
[0129] Furthermore, in the superabsorbent polymer disclosed herein, when 1 g of particles with a particle size of 300 μm to 425 μm swells in water with a conductivity of 110 μS / cm for 1 minute, the free swelling capacity of the superabsorbent polymer that it can hold in water can be 120 g or more, 125 g or more, 130 g or more, or 135 g or more, as well as 230 g or less, 225 g or less, 220 g or less, or 215 g or less.
[0130] The method used to measure the absorption rate in water with a conductivity of 110 µS / cm will be described in more detail in the Experimental Examples section, which will be described later.
[0131] Furthermore, the factor values F1 and F2, which represent the relationship between centrifugation retention capacity (CRC), aspect ratio (A / R), convexity, and roundness according to this disclosure, can be achieved by controlling the composition / content of the superabsorbent polymer, the preparation process conditions of the superabsorbent polymer, etc.
[0132] For example, the factor values F1 and F2, which represent the relationship between centrifugal retention capacity (CRC), aspect ratio (A / R), convexity, and roundness, can be controlled to have a specific range by controlling the type and content of monomer composition during polymerization, the type and timing of surfactant introduction in the micronization step, and the type, rotation speed, pore size, and number of micronization cycles of the micronization device.
[0133] This will be described in more detail in Project II, Methods for the Preparation of Superabsorbent Polymers.
[0134] The components that make up the superabsorbent polymer will be described in more detail below.
[0135] One aspect of this disclosure is a polyacrylic acid (salt)-based superabsorbent polymer comprising a base polymer comprising a water-soluble olefinically unsaturated monomer having an acidic group and a crosslinking agent. The crosslinking polymer can be formed by polymerizing a monomer composition comprising components such as monomers, an internal crosslinking agent, and a polymerization initiator.
[0136] Here, the water-soluble olefinically unsaturated monomer can be any monomer commonly used to prepare superabsorbent polymers. As a non-limiting example, the water-soluble olefinically unsaturated monomer can be a compound represented by Formula 1 below.
[0137] [Formula 1]
[0138] R-COOM'
[0139] In Equation 1 above,
[0140] R is a hydrocarbon group containing 2 to 5 carbon atoms and an unsaturated bond, and
[0141] M' can be a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.
[0142] For example, the monomer can be (meth)acrylic acid, and one or more of the monovalent (alkali) metal salts, divalent metal salts, ammonium salts and organic amine salts of these acids.
[0143] If (meth)acrylic acid and / or its salts are used as water-soluble olefinic unsaturated monomers as described above, it is advantageous in obtaining superabsorbent polymers with improved absorbency. Furthermore, maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, or 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamide, N-substituted (meth)acrylates, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxy polyethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, (N,N)-dimethylaminoethyl (meth)acrylate, (N,N)-dimethylaminopropyl (meth)acrylamide, etc., can be used as monomers.
[0144] Water-soluble olefinically unsaturated monomers possess acidic groups. In the preparation of superabsorbent polymers, the polymer is formed by crosslinking monomers in which at least a portion of the acidic groups are neutralized by a neutralizing agent. However, in this disclosure, the acidic groups may not be neutralized during polymerization, but rather after polymer formation. More specific details regarding this will be provided in the section concerning methods for preparing superabsorbent polymers.
[0145] The concentration of the water-soluble olefinic unsaturated monomer in the monomer composition can be appropriately adjusted taking into account polymerization time, reaction conditions, etc., and can be from about 20% to about 60% by weight, or from about 20% to about 40% by weight.
[0146] As used herein, the term "internal crosslinker" is used to distinguish it from the surface crosslinker used to crosslink the surface of superabsorbent polymer particles, which will be described later, and the internal crosslinker is used to form a polymer containing a crosslinked structure by introducing crosslinking bonds between the unsaturated bonds of the aforementioned water-soluble olefinic unsaturated monomers.
[0147] The crosslinking in the above steps is carried out without distinction between the surface and the interior. However, if the surface crosslinking process of the superabsorbent polymer particles, which will be described later, is performed, the surface of the finally prepared superabsorbent polymer particles may contain newly crosslinked structures through the surface crosslinking agent, and the interior of the superabsorbent polymer particles may retain the crosslinked structures through the internal crosslinking agent.
[0148] According to one aspect of this disclosure, the internal crosslinking agent may include one or more of a multifunctional acrylate-based compound, a multifunctional allyl-based compound, or a multifunctional vinyl-based compound.
[0149] Non-limiting examples of multifunctional acrylate-based compounds may include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, pentaerythritol di(meth)acrylate, and ethylene glycol di(meth)acrylate. Acrylates, pentaerythritol tri(meth)acrylates, pentaerythritol tetra(meth)acrylates, dipentaerythritol di(meth)acrylates, dipentaerythritol tri(meth)acrylates, dipentaerythritol tetra(meth)acrylates, dipentaerythritol penta(meth)acrylates, trimethylolpropane di(meth)acrylates, trimethylolpropane tri(meth)acrylates, glycerol di(meth)acrylates, glycerol tri(meth)acrylates, etc., and any one of them may be used alone, or a mixture of two or more of them may be used.
[0150] Non-limiting examples of multifunctional allyl-based compounds may include ethylene glycol diallyl ether, diethylene glycol diallyl ether, triethylene glycol diallyl ether, tetraethylene glycol diallyl ether, polyethylene glycol diallyl ether, propylene glycol diallyl ether, tripropylene glycol diallyl ether, polypropylene glycol diallyl ether, butanediol diallyl ether, butanediol diallyl ether, hexanediol diallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, pentaerythritol tetraallyl ether, dipentaerythritol diallyl ether, dipentaerythritol triallyl ether, dipentaerythritol tetraallyl ether, dipentaerythritol pentaallyl ether, trimethylolpropane diallyl ether, trimethylolpropane triallyl ether, glycerol diallyl ether, glycerol triallyl ether, etc., and any one of them may be used alone, or a mixture of two or more of them may be used.
[0151] Non-limiting examples of multifunctional vinyl-based compounds may include ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, tetraethylene glycol divinyl ether, polyethylene glycol divinyl ether, propylene glycol divinyl ether, tripropylene glycol divinyl ether, polypropylene glycol divinyl ether, butanediol divinyl ether, butanediol divinyl ether, hexanediol divinyl ether, pentaerythritol divinyl ether, pentaerythritol trivinyl ether, pentaerythritol tetravinyl ether, dipentaerythritol divinyl ether, dipentaerythritol trivinyl ether, dipentaerythritol tetravinyl ether, dipentaerythritol pentavinyl ether, trimethylolpropane divinyl ether, trimethylolpropane trivinyl ether, glycerol divinyl ether, glycerol trivinyl ether, etc., and any one of them may be used alone, or a mixture of two or more of them may be used. For example, pentaerythritol triallyl ether may be used.
[0152] In the aforementioned multifunctional allyl-based or vinyl-based compounds, two or more unsaturated groups contained in the molecule can be bonded to the unsaturated bonds of a water-soluble olefinic unsaturated monomer or to the unsaturated bonds of another internal crosslinking agent, thereby forming a crosslinked structure during the polymerization process. Unlike acrylate-based compounds containing ester bonds (-(C=O)O-) in the molecule, the crosslinking bonds can be maintained more stably even during the neutralization process after the polymerization reaction, as will be described later.
[0153] Therefore, the gel strength of the prepared superabsorbent polymer can be improved, the processing stability during the discharge process after polymerization can be improved, and the amount of extractable contents can be minimized.
[0154] In the presence of the aforementioned internal crosslinking agent, the crosslinking polymerization of water-soluble olefinic unsaturated monomers can be carried out in the presence of a polymerization initiator and (if necessary) thickeners, plasticizers, preservation stabilizers, antioxidants, etc.
[0155] In the monomer composition, based on 100 parts by weight of water-soluble olefinic unsaturated monomer, the aforementioned internal crosslinking agent can be used in amounts from 0.01 parts by weight to 5 parts by weight. For example, the internal crosslinking agent can be used in amounts of 0.01 parts by weight or more, 0.05 parts by weight or more, or 0.1 parts by weight or more, and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.7 parts by weight or less. If the content of the internal crosslinking agent is too low, crosslinking cannot be sufficiently achieved, making it difficult to achieve an appropriate level or higher strength; and if the content of the internal crosslinking agent is too high, the internal crosslinking density increases, making it difficult to achieve the desired centrifugal retention capacity. In particular, within the above ranges, it is suitable to achieve the factor values F1 and F2 of this disclosure, which represent the relationship between centrifugal retention capacity (CRC), aspect ratio (A / R), convexity, and roundness, within the desired range.
[0156] Polymers formed using such internal crosslinking agents have a three-dimensional network structure in which the main chain formed by the polymerization of water-soluble olefinic unsaturated monomers is crosslinked by the internal crosslinking agent. As described above, if the polymer has a three-dimensional network structure, the centrifugal retention capacity and pressure absorption rate of the superabsorbent polymer can be significantly improved compared to a two-dimensional linear structure in which no further crosslinking is performed by the internal crosslinking agent.
[0157] The polymer is prepared by polymerizing monomers and an internal crosslinker in the presence of a polymerization initiator, and there is no particular limitation on the type of polymerization initiator. However, for example, polymerization can be carried out using a thermal polymerization method in a batch reactor, so a thermal polymerization initiator can be used as the polymerization initiator.
[0158] As a thermal polymerization initiator, one or more initiators selected from persulfate-based initiators, azo-based initiators, hydrogen peroxide, and ascorbic acid can be used. Specifically, examples of persulfate-based initiators include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), ammonium persulfate ((NH4)2S2O8), etc., and examples of azo-based initiators include 2,2-azobis(2-amidinepropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoylazo)isobutyronitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 4,4-azobis-(4-cyanopentanoic acid), etc. Many more different thermal polymerization initiators are described in detail on page 203 of 'Principle of Polymerization' by Odian (Wiley, 1981), and are not limited to the examples mentioned above.
[0159] Based on 100 parts by weight of water-soluble olefinically unsaturated monomers, the above-mentioned polymerization initiator can be used in an amount of 2 parts by weight or less. That is, if the concentration of the polymerization initiator is too low, the polymerization rate may decrease, and a large amount of residual monomer may be extracted into the final product. Conversely, if the concentration of the polymerization initiator is higher than the above range, the polymer chains forming the network may become shorter, thereby deteriorating the physical properties of the polymer, such as increasing the content of extractable contents and reducing the absorption rate under pressure.
[0160] Meanwhile, in one aspect of this disclosure, polymerization can be initiated by introducing the aforementioned polymerization initiator and reducing agent, which form a redox pair, together into the monomer composition.
[0161] Specifically, the initiator and the reducing agent react with each other and form free radicals when introduced into the polymer solution.
[0162] The free radicals formed react with the monomers, and because the redox reaction between the initiator and the reducing agent is highly reactive, polymerization is initiated even when only trace amounts of initiator and reducing agent are introduced. Therefore, it is not necessary to increase the process temperature, which allows for low-temperature polymerization and minimizes changes in the physical properties of the polymer solution.
[0163] Polymerization reactions utilizing redox reactions can proceed smoothly even at temperatures close to or below room temperature (25°C). For example, polymerization reactions can be carried out at temperatures between 5°C and 25°C or between 5°C and 20°C.
[0164] In one aspect of this disclosure, if a persulfate-based initiator is used as the initiator, the reducing agent may be selected from one or more of the following: sodium metabisulfite (Na2S2O5); tetramethylethylenediamine (TMEDA); a mixture of ferrous(II) sulfate and EDTA (FeSO4 / EDTA); sodium formaldehyde sulfoxylate; and disodium 2-hydroxy-2-sulfinylate.
[0165] As an example, potassium persulfate can be used as an initiator and disodium 2-hydroxy-2-sulfinylacetate can be used as a reducing agent; ammonium persulfate can be used as an initiator and tetramethylethylenediamine can be used as a reducing agent; sodium persulfate can be used as an initiator and sodium formaldehyde sulfoxylate can be used as a reducing agent.
[0166] In another aspect of this disclosure, when a hydrogen peroxide-based initiator is used as the initiator, the reducing agent may be selected from one or more of the following: ascorbic acid; sucrose; sodium sulfite (Na2SO3); sodium metabisulfite (Na2S2O5); tetramethylethylenediamine (TMEDA); a mixture of ferrous(II) sulfate and EDTA (FeSO4 / EDTA); sodium formaldehyde sulfoxylate; disodium 2-hydroxy-2-sulfinacetic acid; and disodium 2-hydroxy-2-sulfinacetic acid.
[0167] If necessary, the above monomer composition may also contain additives, such as thickeners, plasticizers, preservation stabilizers, antioxidants, etc.
[0168] Furthermore, the monomer composition containing the monomer can be, for example, in the form of a solution dissolved in a solvent such as water, and the solid content (i.e., the concentration of monomer, internal crosslinking agent, and polymerization initiator) in the monomer composition in the above-mentioned solution state can be appropriately adjusted taking into account polymerization time, reaction conditions, etc. For example, the solid content in the monomer composition can be from 10% to 80% by weight, from 15% to 60% by weight, or from 30% to 50% by weight.
[0169] The solvents that can be used at this time are not restricted in terms of composition, as long as the solvent can dissolve the above components. For example, one or more of the following can be used in combination: water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl pentyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide, etc.
[0170] Because the olefinic unsaturated monomers are polymerized in an unneutralized state, the polymers obtained by the above method can form polymers with high molecular weight and uniform molecular weight distribution, and because the content of extractable contents is reduced, it is suitable to achieve the factor values F1 and F2 (which are target values) of this disclosure, which represent the relationship between centrifugation retention capacity (CRC), aspect ratio (A / R), convexity and roundness, within the desired range.
[0171] In addition, the water content of the polymer can be from 30% to 80% by weight. For example, the water content of the polymer can be 30% or more by weight, 45% or more by weight, or 50% or more by weight, as well as 80% or less by weight, 70% or less by weight, or 60% or less by weight.
[0172] If the polymer has too low a moisture content, it will be difficult to obtain an adequate surface area in the pulverization step, which may prevent effective pulverization. If the polymer has too high a moisture content, the pressure applied in the pulverization step may increase, making it difficult to pulverize to the desired particle size.
[0173] Throughout this specification, the term "moisture content" refers to the amount of water relative to the total weight of the polymer, obtained by subtracting the weight of the polymer in its dry state from the weight of the polymer itself. Specifically, moisture content is defined as a value calculated by measuring the weight loss due to evaporation of moisture from the polymer during a drying process involving raising the temperature of the polymer in its crumbly state via infrared heating. The drying conditions involve raising the temperature from room temperature to approximately 180°C, maintaining the temperature at 180°C, and setting the total drying time to 40 minutes (including 5 minutes for raising the temperature), after which the moisture content is measured.
[0174] The superabsorbent polymer according to one aspect of this disclosure comprises: the aforementioned base polymer powder containing a crosslinked polymer of a water-soluble olefinic unsaturated monomer having an acidic group and an internal crosslinking agent; and a surface crosslinked layer formed on the base polymer powder by further crosslinking the crosslinked polymer with a surface crosslinking agent.
[0175] A surface crosslinking layer is formed on at least a portion of the surface of the base polymer powder, and can be formed by further crosslinking the crosslinked polymer contained in the base polymer powder with a surface crosslinking agent.
[0176] As a surface crosslinking agent, any surface crosslinking agent used in the preparation of superabsorbent polymers can be used without particular limitation. For example, the surface crosslinking agent may include: at least one polyol selected from ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol, and glycerol; at least one carbonate-based compound selected from ethylene carbonate, propylene carbonate, and glycerol carbonate; and an epoxy compound, such as ethylene glycol diglycidyl ether. Azoline compounds, for example azole ketones; polyamine compounds; monoamines 2-oxazolidinone, dioxazolidinone azole ketones or polyoxinones Azoxyl ketone compounds; cyclic urea compounds; etc.
[0177] Specifically, one or more, two or more, or three or more of the above-mentioned surface crosslinking agents can be used as surface crosslinking agents. For example, ethylene carbonate-propylene carbonate (ECPC), propylene glycol and / or glycerol carbonate can be used.
[0178] Based on 100 parts by weight of superabsorbent polymer particles, the aforementioned surface crosslinking agent can be used in an amount from about 0.001 parts by weight to about 5 parts by weight. For example, based on 100 parts by weight of superabsorbent polymer particles, the surface crosslinking agent can be used in amounts of 0.005 parts by weight or more, 0.01 parts by weight or more, or 0.05 parts by weight or more, and 5 parts by weight or less, 4 parts by weight or less, or 3 parts by weight or less. In order to prepare a superabsorbent polymer exhibiting excellent overall absorption physical properties, the content range of the surface crosslinking agent can be adjusted within the aforementioned range. In particular, within the aforementioned range, it is suitable to achieve the factor values F1 and F2, which represent the relationship between centrifugal retention capacity (CRC), aspect ratio (A / R), convexity, and roundness of the present disclosure, within the desired range.
[0179] Furthermore, the surface crosslinking layer can be formed by adding inorganic materials to the surface crosslinking agent. That is, in the presence of the surface crosslinking agent and inorganic materials, the surface crosslinking layer can be formed by further crosslinking the surface of the base polymer powder.
[0180] As the aforementioned inorganic material, one or more inorganic materials selected from silica, clay, alumina, silica-alumina composites, titanium dioxide, zinc oxide, and aluminum sulfate can be used. The aforementioned inorganic material can be used in powder or liquid form, and in particular, can be used as alumina powder, silica-alumina powder, titanium dioxide powder, or nano-silica solution. Furthermore, based on 100 parts by weight of superabsorbent polymer particles, the inorganic material can be used in an amount from about 0.001 parts by weight to about 1 part by weight.
[0181] As described above, by controlling the factor values F1 and F2 (which are parameters of the present disclosure described above) representing the relationship between centrifugation retention capacity (CRC), aspect ratio (A / R), convexity, and roundness to a desired range, the superabsorbent polymer comprising a base polymer powder and a surface cross-linked layer formed on the base polymer powder can absorb excreted bodily fluids at high speed when applied to hygiene products such as diapers, and can also absorb a relatively large amount of bodily fluids at the beginning, and thus can prevent problems such as the accumulation of bodily fluids in the hygiene product or their leakage to the outside.
[0182] II. Methods for preparing superabsorbent polymers
[0183] Meanwhile, commonly used superabsorbent polymers are prepared by crosslinking and polymerizing water-soluble olefinic unsaturated monomers with at least partially neutralized acidic groups in the presence of an internal crosslinking agent and a polymerization initiator to form a hydrogel polymer. The resulting hydrogel polymer is then dried and pulverized to the desired particle size. Typically, to promote drying and improve the efficiency of the pulverization process, a chopping process is performed before drying, cutting the hydrogel polymer into particles several millimeters in size. However, during this chopping process, due to the adhesiveness of the hydrogel polymer, it cannot be pulverized to the micrometer-sized particle level and becomes an aggregated gel. When the hydrogel polymer in its aggregated gel form is dried, a plate-like dried body is formed. To pulverize it to the micrometer-sized particle level, a multi-stage pulverization process can be performed to reduce the polymer's adhesiveness, but this process generates a large amount of fine powder.
[0184] Specifically, commonly used superabsorbent polymers are prepared through the following steps.
[0185] (Neutralization) Neutralizes at least a portion of the acidic groups in a water-soluble olefinic unsaturated monomer;
[0186] (Polymerization) In the presence of an internal crosslinking agent and a polymerization initiator, a water-soluble olefinic unsaturated monomer having at least partially neutralized acidic groups is crosslinked and polymerized to form a hydrogel polymer.
[0187] (Chopping) Chop the hydrogel polymer;
[0188] (Drying) Drying the shredded hydrogel polymer; and
[0189] (Crushing / Grading) The dried polymer is crushed and graded into normal particles and fine powder.
[0190] As described above, the shredded hydrogel polymer has the form of aggregated gels with a size of about 1 cm to about 10 cm. The shredded hydrogel polymer is stacked on a belt formed of a porous plate and then dried by hot air supplied from the top or bottom. Since the polymer dried by the above drying method exhibits a plate-like shape rather than a granular shape, pulverization and subsequent classification are carried out in the following steps: coarse pulverization followed by classification, then fine pulverization followed by classification, so that the prepared particles become normal particles, i.e., particles with a particle size of 150 μm to 850 μm. Since the amount of fine powder separated in the final classification step by the above preparation method is as high as about 20% to about 30% by weight based on the total weight of the finally prepared superabsorbent polymer, the separated fine powder is recombined by mixing with an appropriate amount of water and then introduced into a step prior to the pulverization or drying step for reuse.
[0191] However, when a fine powder recombinant mixed with water is introduced during the pulverization or drying process for reuse, there are problems that increase equipment load and / or energy consumption, and cause deterioration of the physical properties of the superabsorbent polymer due to unclassified residual fine powder.
[0192] As a result of repeated research to address the aforementioned problems, it was determined that instead of polymerizing in a state where the acidic groups of the water-soluble olefinic unsaturated monomers are neutralized, as is commonly done in methods for preparing superabsorbent polymers, polymerization is first carried out in a state where the acidic groups are not neutralized to form a polymer, and the hydrogel polymer is micronized in the presence of a surfactant, followed by neutralization of the acidic groups of the polymer, or neutralization of the acidic groups of the polymer to form a hydrogel polymer, followed by micronization of the hydrogel polymer in the presence of a surfactant, or neutralization of the acidic groups present in the polymer simultaneously with micronization, a large amount of surfactant is present on the surface of the polymer, and this is sufficient to reduce the high adhesion of the polymer, thereby preventing excessive aggregation of the polymer and controlling the aggregation state to a desired level.
[0193] At this point, if ultrafine pulverization is performed by applying high-intensity mechanical shear force during the micronization step, aggregated hydrogel particles with finer pores can be formed.
[0194] The hydrogel polymer, prepared by ultrafine pulverization by applying high-intensity mechanical shear force, is prepared in the form of stable micropores with 100 μm or smaller, and then subsequently managed under milder conditions for pulverization and drying, which allows for a further reduction in the amount of fine powder generated during the process.
[0195] Furthermore, by using an ultrafine pulverization process with high-intensity mechanical shear force, micropores can be formed in the hydrogel polymer during the polymerization step without the use of a separate foaming agent, thereby improving the vortex time and thus making it easy to control the factor values F1 and F2, which represent the relationship between centrifugal retention capacity (CRC), aspect ratio (A / R), convexity and roundness as disclosed above, within the desired range.
[0196] Meanwhile, the hydrogel micronization process can be carried out in the presence of surfactants. By using surfactants in the micronization step, particle aggregation can be effectively controlled, and thus productivity can be further improved by reducing equipment load.
[0197] Furthermore, when polymers are formed by first polymerizing in an unneutralized state and then neutralizing the acidic groups present in the polymer, polymers with longer chains can be formed, which can reduce the content of extractable contents existing in an uncrosslinked state due to incomplete crosslinking.
[0198] Because extractable contents tend to flow out easily when superabsorbent polymers come into contact with liquids, if the extractable content is high, most of the flowed extractable contents remain on the surface of the superabsorbent polymer, making it sticky and reducing its permeability. Therefore, maintaining a low extractable content is important for permeability.
[0199] According to one aspect of this disclosure, since polymerization is carried out in an unneutralized state, the content of extractable contents is reduced, which improves the permeability of the superabsorbent polymer and thus makes it easier to control the roundness and aspect ratio within the desired range.
[0200] The following sections describe in more detail a method for preparing superabsorbent polymers according to one aspect, focusing on each step.
[0201] Step 1: Aggregation Step
[0202] First, a monomer composition comprising a water-soluble olefinic unsaturated monomer with acidic groups and an internal crosslinking agent is polymerized to prepare a basic polymer powder in which the water-soluble olefinic unsaturated monomer with acidic groups and the internal crosslinking agent are crosslinked.
[0203] The above steps may include mixing a water-soluble olefinic unsaturated monomer having an acidic group, an internal crosslinking agent, and a polymerization initiator to prepare a monomer composition, and polymerizing the monomer composition to form a polymer.
[0204] Here, the same content described in Project I above regarding superabsorbent polymers can be applied equally to each component.
[0205] Meanwhile, the water-soluble olefinically unsaturated monomer has acidic groups. As described above, in the preparation of commonly used superabsorbent polymers, monomers in which at least a portion of the acidic groups have been neutralized by a neutralizing agent are crosslinked to form a polymer. Specifically, in the step of mixing the water-soluble olefinically unsaturated monomer having acidic groups, the internal crosslinking agent, the polymerization initiator, and the neutralizing agent, at least a portion of the acidic groups of the water-soluble olefinically unsaturated monomer has been neutralized.
[0206] However, according to one aspect of this disclosure, the polymer is formed by first polymerizing the water-soluble olefinic unsaturated monomer in a state in which the acidic groups are not neutralized.
[0207] Water-soluble olefinic unsaturated monomers (e.g., acrylic acid) in which the acidic groups are not neutralized are liquid at room temperature and highly miscible with the solvent (water), thus existing in a mixed solution state in the monomer composition. However, water-soluble olefinic unsaturated monomers in which the acidic groups are neutralized are solid at room temperature and have different solubilities depending on the temperature of the solvent (water), with decreasing solubility as the temperature decreases.
[0208] Water-soluble olefinic unsaturated monomers with unneutralized acidic groups exhibit higher solubility or miscibility with the solvent (water) compared to monomers with neutralized acidic groups. Consequently, they do not precipitate even at low temperatures, thus facilitating long-term polymerization at low temperatures. Therefore, by using water-soluble olefinic unsaturated monomers in the unneutralized state for long-term polymerization, polymers with high molecular weight and uniform molecular weight distribution can be stably formed.
[0209] Furthermore, polymers with longer chains can be formed, which can reduce the content of extractable contents that exist in an uncrosslinked state due to incomplete polymerization or crosslinking, and thus is suitable for achieving the saturation absorption rate (which is a new parameter of the present disclosure) within the desired range.
[0210] Furthermore, as described above, if polymerization is first carried out in a state where the acidic groups of the monomers are not neutralized to form a polymer, and the polymer is neutralized, and then micronized in the presence of a surfactant, or micronized in the presence of a surfactant and then neutralized, or micronized simultaneously with neutralizing the acidic groups present in the polymer, then a large amount of surfactant is present on the surface of the polymer, thereby effectively reducing the adhesiveness of the polymer.
[0211] According to one aspect of this disclosure, the step of polymerizing the monomer composition to form a polymer can be carried out in a batch reactor for 1 hour or longer.
[0212] Among the common methods used to prepare superabsorbent polymers, the polymerization methods are broadly classified into thermal polymerization and photopolymerization, depending on the source of polymerization energy. Typically, thermal polymerization can be carried out in a reactor with a stirring shaft, such as a kneader, while photopolymerization can be carried out in a flat-bottomed container.
[0213] Meanwhile, if polymerization is carried out as a continuous polymerization, for example, if polymerization is carried out in a reactor with a conveyor belt, new monomer compositions are supplied to the reactor as the polymerization products move, thereby achieving polymerization in a continuous manner. This results in the mixing of polymers with different polymerization rates, and therefore makes it difficult to achieve uniform polymerization throughout the monomer composition, which may lead to deterioration of overall physical properties.
[0214] However, according to one aspect of this disclosure, polymerization is carried out in a fixed manner in a batch reactor, which reduces the risk of mixing polymers with different polymerization rates and thus allows for the acquisition of polymers with uniform quality.
[0215] Furthermore, compared to the case where polymerization is carried out continuously in a reactor with a conveyor belt, the above-described polymerization step is conducted in a batch reactor with a predetermined volume, and the polymerization reaction lasts for a long period of time, such as 1 hour or longer, 3 hours or longer, or 6 hours or longer. Although the polymerization reaction time is long as described above, because the polymerization is carried out on unneutralized water-soluble olefinic unsaturated monomers, the monomers are not prone to precipitation even when polymerization is carried out for a long time, thus facilitating long-term polymerization.
[0216] Meanwhile, the polymerization in the batch reactor disclosed herein is carried out by a thermal polymerization method, therefore a thermal polymerization initiator is used as the polymerization initiator, and the description of the corresponding components is the same as above.
[0217] Steps 2 and 3: Micronization and Neutralization Steps
[0218] Next, the step of micronizing the hydrogel polymer in the presence of a surfactant to prepare a mixture comprising the micronized hydrogel polymer is included (Step 2).
[0219] The micronization step described above is a step of micronizing the polymer in the presence of a surfactant, and it is a step of simultaneously micronizing and aggregating the polymer into a size of tens to hundreds of micrometers, rather than cutting the polymer into a size of millimeters.
[0220] That is, it involves imparting appropriate adhesiveness to the polymer to prepare secondary aggregated particles in the form of primary particles aggregated into particles with a size of tens to hundreds of micrometers. The aqueous superabsorbent polymer particles prepared in the above steps have a normal particle size distribution and a significantly increased surface area, which can significantly improve the absorption rate.
[0221] Meanwhile, if ultrafine grinding is performed in the micronization step by applying high-intensity mechanical shear force at a rotation speed of 500 rpm to 4,000 rpm, aggregated hydrogel particles with finer pores can be formed.
[0222] At this point, if ultrafine grinding is performed at a speed of 500 rpm to 4,000 rpm, high-intensity mechanical shear force is applied, making it easy to form micropores of 100 μm or smaller on the polymer. Therefore, the surface roughness increases, and the total surface area of the polymer increases significantly due to the pores formed inside and outside the polymer particles. Since the micropores form with a stable shape compared to the pores formed using a foaming agent in the polymerization step, the degree of fine powder generation due to the corresponding pores can be significantly reduced in subsequent processes. The superabsorbent polymer particles prepared in the above steps have a significantly increased surface area, which allows for a significant improvement in vortex time, and therefore, it is suitable to achieve the factor values F1 and F2, which represent the relationship between centrifugal retention capacity (CRC), aspect ratio (A / R), convexity, and roundness as disclosed above, within the desired range.
[0223] The ultrafine grinding process is carried out at speeds of 500 rpm to 4,000 rpm. If the speed is less than 500 rpm, it is difficult to form sufficient pores of the desired degree, making it difficult to predict rapid vortex times and ensure the desired level of productivity. Furthermore, if the speed is greater than 4,000 rpm, the polymer chains may be damaged due to excessive shear forces, thus increasing the content of extractable contents and potentially slightly degrading the overall physical properties of the prepared superabsorbent polymer. For example, the ultrafine grinding process can be carried out at speeds of 1,000 rpm to 3,500 rpm or 2,000 rpm to 3,000 rpm. Within these ranges, the desired micropores are easily formed without any of the aforementioned problems.
[0224] According to one aspect of this disclosure, the micronization step is performed by a micronization apparatus, which may include: a main body having a transfer space therein in which polymer is transferred; a screw member rotatably mounted inside the transfer space to move the polymer; a drive motor providing rotational driving force to the screw member; a cutter member mounted in the main body and pulverizing the polymer; and a perforated plate having a plurality of holes discharging the polymer pulverized by the cutter member to the outside of the main body.
[0225] At this time, the size of the holes in the porous plate of the micronization device can be 1 mm to 25 mm, 5 mm to 20 mm, or 5 mm to 15 mm.
[0226] As described above, when a micronization device is used to micronize a polymer mixed with a surfactant while controlling aggregation, a smaller particle size distribution is achieved, allowing subsequent drying and pulverization processes to be carried out under milder conditions. Consequently, the physical properties of the superabsorbent polymer can be improved while preventing the formation of fine powder. Furthermore, if ultrafine pulverization is performed, appropriate micropores are simultaneously formed on the polymer surface, allowing the absorption rate to be improved through the increase in surface area.
[0227] The micronization step can be performed once or more, for example, 1 to 6 times, 1 to 4 times, or 1 to 3 times. The above steps can be performed using a plurality of micronization devices, or using a single micronization device comprising a plurality of perforated plates and / or a plurality of cutter components, or some of the devices in the plurality of micronization devices may include a plurality of perforated plates and / or a plurality of cutter components.
[0228] According to one aspect of this disclosure, a surfactant can be used in the above-mentioned micronization step, thereby effectively controlling the aggregation between polymer particles to reduce the load on the equipment used in the pulverization process, thus further improving productivity.
[0229] For example, the surfactant may be a compound represented by Formula 2 below or a salt thereof, but this disclosure is not limited thereto.
[0230] [Equation 2]
[0231]
[0232] In equation 2 above,
[0233] A1, A2, and A3 are each independently a single bond, a carbonyl group, and... , ,or However, one or more of them are carbonyl or Where m1, m2, and m3 are each independent integers from 1 to 8. Connected to each adjacent oxygen atom, and Connect to each adjacent R1, R2, and R3.
[0234] R1, R2, and R3 are each independently hydrogen, a straight-chain or branched alkyl group having 6 to 18 carbon atoms, or a straight-chain or branched alkenyl group having 6 to 18 carbon atoms, and
[0235] n is an integer from 1 to 9.
[0236] The surfactant is mixed with the polymer and added in a way that promotes the micronization process without agglomeration.
[0237] The surfactant represented by Equation 2 above is a nonionic surfactant, and it exhibits excellent surface adsorption properties through hydrogen binding forces even in the case of unneutralized polymers, thus making it suitable for achieving the desired aggregation control effect. On the other hand, in the case of anionic surfactants instead of nonionic surfactants, when mixed with polymers neutralized by a neutralizing agent (e.g., NaOH or Na₂SO₄), the anionic surfactant utilizes the Na₂O₃ ionized in the carboxyl substituents of the polymer... + Ions are adsorbed as a medium, and when mixed with unneutralized polymers, there is a problem that the adsorption efficiency of the polymer is relatively degraded due to competition with the anions of the carboxyl substituents of the polymer.
[0238] Specifically, in the surfactant represented by Formula 2 above, the hydrophobic functional group is the terminal functional group R1, R2, or R3 (if not hydrogen), and the hydrophilic functional group also includes the glycerol-derived portion in the chain and the terminal hydroxyl group (if A...). n It is a single bond, and R at the same time n (where n = 1 to 3), where the glycerol-derived moiety and the terminal hydroxyl groups are hydrophilic functional groups, which are used to improve the adsorption properties on the polymer surface. Therefore, the aggregation of superabsorbent polymer particles can be effectively suppressed.
[0239] In Formula 2 above, the hydrophobic functional groups R1, R2, and R3 (if not hydrogen) are each independently a straight-chain or branched alkyl group having 6 to 18 carbon atoms, or a straight-chain or branched alkenyl group having 6 to 18 carbon atoms. In this case, if R1, R2, or R3 (if not hydrogen) is an alkyl or alkenyl group having fewer than 6 carbon atoms, there is a problem of ineffective control over the aggregation of pulverized particles due to the short chain length. Furthermore, if R1, R2, or R3 (if not hydrogen) is an alkyl or alkenyl group having more than 18 carbon atoms, the mobility of the surfactant decreases. Therefore, the surfactant may not mix effectively with the polymer, and the unit cost of the composition may increase due to the increased cost of the surfactant.
[0240] For example, R1, R2, or R3 may be hydrogen, or, in the case of a straight-chain or branched alkyl group having 6 to 18 carbon atoms, may be 2-methylhexyl, n-heptyl, 2-methylheptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecanyl, n-hexadecyl, n-heptadecyl, or n-octadecyl; or, in the case of a straight-chain or branched alkenyl group having 6 to 18 carbon atoms, may be 2-hexenyl, 2-heptenyl, 2-octenyl, 2-nonenyl, n-decenyl, 2-undecenyl, 2-dodecenyl, 2-tweldecenyl, 2-tetradecenyl, 2-pentadecanenyl, 2-hexadecenyl, 2-heptadecenyl, or 2-octadecenyl.
[0241] Surfactants can be selected from compounds represented by formulas 2-1 to 2-14.
[0242] [Equation 2-1]
[0243]
[0244] [Equation 2-2]
[0245]
[0246] [Equation 2-3]
[0247]
[0248] [Equation 2-4]
[0249]
[0250] [Equation 2-5]
[0251]
[0252] [Equation 2-6]
[0253]
[0254] [Equation 2-7]
[0255]
[0256] [Equation 2-8]
[0257]
[0258] [Equation 2-9]
[0259]
[0260] [Equation 2-10]
[0261]
[0262] [Equation 2-11]
[0263]
[0264] [Equation 2-12]
[0265]
[0266] [Equation 2-13]
[0267]
[0268] [Equation 2-14]
[0269] .
[0270] Meanwhile, there are no particular restrictions on the amount of surfactant to be used, but depending on the productivity assurance or equipment load, the surfactant can be used in amounts from 0.06 g to 0.48 g per 1,000 g of hydrogel polymer.
[0271] If too little surfactant is used, it cannot be uniformly adsorbed onto the polymer surface, potentially causing particle re-aggregation after pulverization. Alternatively, excessive surfactant-polymer sharing can degrade absorption performance, such as centrifugal retention capacity and absorption rate under pressure. Conversely, if too much surfactant is used, the overall physical properties of the resulting superabsorbent polymer may be compromised due to reduced surface tension.
[0272] Therefore, for example, the surfactant can be used in amounts of 0.06 g or more, 0.1 g or more, or 0.2 g or more, and 0.48 g or less, 0.45 g or less, or 0.4 g or less per 1,000 g of hydrogel polymer, and thus, the roundness and aspect ratio of the present disclosure described above can be easily controlled within the desired range.
[0273] There are no particular limitations on the method used to mix surfactants with polymers, as long as it is a method that can uniformly mix surfactants and polymers and can be appropriately employed and used. Specifically, surfactants can be mixed in a dry manner, dissolved in a solvent and then mixed in a solution state, or the surfactant can be melted and then mixed.
[0274] In the above, the surfactant can be mixed, for example, in a solution dissolved in a solvent. In this case, all types of solvents can be used, whether inorganic or organic; however, water is most suitable considering the ease of the drying process and the cost of the solvent recovery system. Furthermore, the solution can be prepared by mixing the surfactant and polymer in a reaction vessel, placing the polymer in a mixer and spraying the solution onto it, or mixing the polymer and solution by continuously supplying them to a continuously operating mixer.
[0275] At the same time, if the surfactant is mixed in a solution dissolved in water, the surfactant can be diluted to an aqueous solution with a concentration of about 0.01% to 90% and used.
[0276] For example, if the surfactant is used at a rate of 0.1 g per 1,000 g of hydrogel polymer, 100 g of a 0.1% aqueous solution can be used by dissolving 0.1 g of surfactant in 99.9 g of water. Alternatively, 10 g of a 1% aqueous solution can be used by dissolving 0.1 g of surfactant in 9.9 g of water.
[0277] That is, if the same amount of surfactant is used, the water content can be adjusted to prepare an aqueous solution with the desired concentration, and the concentration can be appropriately adjusted taking into account the physical properties of the superabsorbent polymer to be prepared.
[0278] According to one aspect of this disclosure, a step (step 3) is performed to neutralize at least a portion of the acidic groups of the polymer, and the micronization of step 2 and the neutralization of step 3 can be performed sequentially, alternately, or simultaneously.
[0279] That is, a neutralizing agent can be introduced into the polymer first to neutralize acidic groups, and then a surfactant can be introduced into the neutralized polymer to micronize the polymer mixed with the surfactant (in the order of step 3->step 2). Alternatively, the neutralizing agent and surfactant can be introduced into the polymer simultaneously to neutralize the polymer and micronize it (steps 2 and 3 can be performed simultaneously). Alternatively, the surfactant can be introduced first, and then the neutralizing agent can be introduced later (in the order of step 2->step 3). Alternatively, the neutralizing agent and surfactant can be introduced alternately. Alternatively, the surfactant can be introduced first for micronization, and then the neutralizing agent can be introduced for neutralization. Furthermore, a surfactant can be added to the neutralized hydrogel polymer to further carry out the micronization process.
[0280] Here, if neutralization is carried out independently of micronization in step 2, neutralization can be performed in such a way that additives are introduced while the polymer is being pulverized. More specifically, a screw extruder comprising a perforated plate with a plurality of holes can be used. Compared to the micronization apparatus used in the micronization step described above, the screw extruder is an apparatus in which pulverization is carried out under mild conditions, and the extruder speed can be from about 150 rpm to about 500 rpm, and the size of the holes in the perforated plate can be from about 3 mm to 25 mm, but this disclosure is not limited thereto.
[0281] The rotational speed of the screw extruder and the orifice size of the perforated plate affect the discharge state of the superabsorbent polymer exiting the extruder, and the particle shape of the superabsorbent polymer can be changed depending on the discharge state.
[0282] In particular, by adjusting the speed of the screw extruder from 150 rpm to 500 rpm, the roundness and aspect ratio of the present disclosure can be controlled within the desired range.
[0283] At this point, as a neutralizing agent, an alkaline substance capable of neutralizing acidic groups can be used, such as sodium hydroxide, potassium hydroxide, ammonium hydroxide, etc.
[0284] Furthermore, the degree of neutralization (referring to the extent to which acidic groups in the polymer are neutralized by the neutralizing agent) can be 50 mol% to 90 mol%, 60 mol% to 85 mol%, 65 mol% to 85 mol%, or 65 mol% to 80 mol%. The range of the degree of neutralization can be changed according to the final physical properties, and by adjusting the degree of neutralization, the absorption rate and absorption performance can be adjusted.
[0285] At this point, if the degree of neutralization is too high, the absorption rate of the superabsorbent polymer may decrease, and the concentration of carboxyl groups on the particle surface may be too low, making it difficult to properly crosslink the surface in subsequent processes, which may reduce the absorption properties or permeability under pressure. On the other hand, if the degree of neutralization is too low, the polymer may have a significantly reduced absorption capacity and may exhibit properties similar to those of difficult-to-handle elastic rubber.
[0286] Meanwhile, in order to neutralize the entire polymer evenly, a certain time interval can be left between the introduction of the neutralizing agent and the micronization process.
[0287] Step 4: Drying Step
[0288] Next, the micronized and neutralized polymer is dried to prepare a base polymer powder (step 4).
[0289] The above steps involve neutralizing at least a portion of the acidic groups of the polymer and drying the moisture in the base polymer powder (which is a polymer obtained by micronizing the polymer).
[0290] In common methods for preparing superabsorbent polymers, a drying step is performed such that the moisture content of the base polymer powder is from about 4% to 20% by weight, from about 4% to about 15% by weight, or from about 6% to about 13% by weight. However, this disclosure is not limited thereto.
[0291] Step 4 above can be performed using a fixed-bed dryer, a mobile dryer, or a combination thereof.
[0292] According to one aspect of this disclosure, step 4 above can be performed by a fixed-bed drying system.
[0293] Fixed-bed drying refers to the following method: the material to be dried is suspended on a base plate that allows air to pass through, such as a perforated iron plate, and then hot air is passed through the material from bottom to top to dry the material.
[0294] Fixed-bed drying, which dries in a plate-like manner without particle flow, makes it difficult to achieve uniform drying using simple hot air flow. Therefore, fixed-bed drying requires precise control of the hot air and temperature to obtain a dried body with a uniform high moisture content. In this disclosure, by changing the direction of the hot air from downward to upward, bending of the plate-like dried body during drying is prevented, thus preventing hot air escape. Furthermore, the drying temperature is varied for each section to ensure uniform drying of the upper, middle, and lower layers within the dried body with a moisture content deviation of 5% or less.
[0295] As a device capable of drying by fixed-bed drying, a belt dryer or the like can be used, but this disclosure is not limited thereto.
[0296] In the case of a fixed-bed drying step, the drying process can be carried out at temperatures of approximately 80°C to approximately 200°C, 90°C to 190°C, or 100°C to 180°C. If the drying temperature is below 80°C, the drying time may become too long, and if the drying temperature is too high (above 200°C), a superabsorbent polymer with a moisture content lower than the desired moisture content may be obtained. Meanwhile, the drying temperature can refer to the temperature of the hot air used or the internal temperature of the apparatus during the drying process.
[0297] According to one aspect of this disclosure, step 4 above can be performed by a mobile drying system.
[0298] Mobile drying refers to a method of drying a material by mechanically agitating it during the drying process. In this method, the direction in which hot air passes through the material can be the same as or different from the direction of material circulation. Alternatively, the material can be dried by circulating it inside the dryer while a hot medium fluid (hot oil) passes through a separate pipe outside the dryer.
[0299] As a device capable of drying by the aforementioned mobile drying method, a horizontal mixer, rotary kiln, paddle dryer, steam tube dryer, or commonly used mobile dryer can be used.
[0300] In the case of a mobile drying step, the drying process can be carried out at temperatures of approximately 100°C to approximately 300°C, 120°C to 280°C, or 150°C to 250°C. If the drying temperature is too low (below 100°C), the drying time may become too long, and if the drying temperature is too high (above 300°C), the superabsorbent polymer chains may be damaged, which may degrade the overall physical properties. In addition, a superabsorbent polymer with a water content lower than the desired water content may be obtained.
[0301] Step 5: Crushing Step
[0302] Next, the dried base polymer powder is pulverized.
[0303] Specifically, the pulverization step can be performed by pulverizing the dry base polymer powder into particles with a normal particle size (i.e., a particle size of 150 μm to 850 μm).
[0304] Crusher used for the above purposes may specifically be a vertical crusher, a turbine cutter, a turbine mill, a rotary shredder, a cutter mill, a disc mill, a fragment crusher, a crusher, a chopper, a disc cutter, etc., but is not limited to the examples mentioned above.
[0305] Alternatively, as a pulverizer, a needle mill, hammer mill, spiral mill, roller mill, disc mill, jog mill, etc. can be used, but the pulverizer is not limited to the above examples.
[0306] Meanwhile, in the preparation method disclosed herein, compared with the commonly used shredding step, superabsorbent polymer particles with small particle size distribution can be achieved in the micronization step. Furthermore, since the moisture content remains relatively high after drying, even when pulverized under mild conditions with relatively low pulverizing force, superabsorbent polymers with a very high content of normal particle sizes of 150 μm to 850 μm can be obtained, and the fine powder generation rate can be greatly reduced.
[0307] Based on total weight, the superabsorbent polymer particles prepared as described above may contain superabsorbent polymer particles (i.e., normal particles) with a particle size of 150 μm to 850 μm in the following amounts: 80% by weight or more, 85% by weight or more, 89% by weight or more, 90% by weight or more, 92% by weight or more, 93% by weight or more, 94% by weight or more, or 95% by weight or more. The particle size of the above polymer particles can be measured according to the method of EDANA WSP 220.3 of the European Disposable Products and Nonwovens Association (EDANA) standard.
[0308] Furthermore, based on total weight, the superabsorbent polymer particles may contain fine powder with a particle size of less than 150 μm in the following amounts: about 20% by weight or less, about 18% by weight or less, about 15% by weight or less, about 13% by weight or less, about 12% by weight or less, about 11% by weight or less, about 10% by weight or less, about 9% by weight or less, about 8% by weight or less, or about 5% by weight or less. This contrasts with the presence of fine powder in amounts greater than about 20% by weight to about 30% by weight when superabsorbent polymers are prepared according to commonly used preparation methods.
[0309] Additive introduction steps
[0310] Additionally, according to one aspect of this disclosure, prior to the drying step (step 4), a step of introducing an additive into the micronized and neutralized polymer may be included.
[0311] The process of introducing additives is the process of improving physical properties by using additional additives within a range that does not inhibit the desired effect, and there are no particular restrictions on the type of additives. For example, polymerization initiators for removing residual monomers, permeability enhancers for improving absorption properties, fine powder anti-caking agents for recycling the generated fine powder, flow enhancers, antioxidants, neutralizers, surfactants, etc. can be used, but additives are not limited to these.
[0312] The additive introduction step can be performed simultaneously with step 2, simultaneously with step 3, after steps 2 and 3, or in at least one of the above steps. If necessary, the additive introduction step can be performed multiple times, and can also be performed once or more in each step.
[0313] If the additive introduction step is performed independently of steps 2 and 3, that is, if it is performed after steps 2 and 3 and before step 4, the additive introduction step can be performed in a manner in which the additive is introduced while the polymer is being pulverized.
[0314] The pulverization in step 5 above can be applied equivalently to the pulverization described above, and in the pulverization step, the additive can be introduced once or multiple times and mixed with the polymer.
[0315] Grading steps
[0316] Next, after the step of pulverizing the base polymer powder (step 5), a step of classifying the pulverized superabsorbent polymer particles according to their particle size may also be included.
[0317] Surface crosslinking steps
[0318] Furthermore, after pulverizing (step 5) and / or classifying the base polymer powder, a step of forming a surface crosslinking layer on at least a portion of the surface of the base polymer particles in the presence of a surface crosslinking agent may be included. Through the above steps, the crosslinked polymer contained in the base polymer powder can be further crosslinked by the surface crosslinking agent, thereby forming a surface crosslinking layer on at least a portion of the surface of the base polymer powder.
[0319] The same content described above for surface crosslinking agents can be applied equally to surface crosslinking agents.
[0320] Furthermore, there are no limitations on the method used to mix the surface crosslinking agent with the base polymer powder. For example, methods in which the surface crosslinking agent and the composition containing the base polymer powder are introduced into a reaction vessel and mixed, methods in which the surface crosslinking agent is sprayed onto the composition, and methods in which the polymer composition and the surface crosslinking agent are continuously supplied to a continuously operating mixer can be used.
[0321] When mixing the surface crosslinking agent and the base polymer powder, water and methanol can be mixed together and added separately. Adding water and methanol has the advantage that the surface crosslinking agent can be uniformly dispersed in the polymer composition. At this point, the content of added water and methanol can be appropriately adjusted to induce uniform dispersion of the surface crosslinking agent, prevent aggregation of the polymer composition, and optimize the surface penetration depth of the crosslinking agent.
[0322] The surface crosslinking process can be carried out at a temperature of about 80°C to about 250°C. More specifically, the surface crosslinking process can be carried out at a temperature of about 100°C to about 220°C, or about 120°C to about 200°C, for about 20 minutes to about 2 hours, or about 40 minutes to about 80 minutes. When the above surface crosslinking process conditions are met, the surface of the superabsorbent polymer particles is fully crosslinked, thereby increasing the absorption rate under pressure.
[0323] There are no particular restrictions on the methods used to raise the temperature of the surface crosslinking reaction.
[0324] Heating can be achieved by supplying a heat medium or by directly supplying a heat source. The types of heat medium that can be used include, but are not limited to, steam, hot air, and heated fluids such as hot oil, and the temperature of the supplied heat medium can be appropriately selected considering the type of heat medium, the heating rate, and the target temperature. Meanwhile, the heat source that can be directly supplied can include heating via electricity or heating via gas, but is not limited to the examples described above.
[0325] Post-processing steps
[0326] According to one aspect of this disclosure, after the step of forming a surface crosslinking layer on at least a portion of the surface of the base polymer powder, the method may be performed by further including any one or more of the following steps: a cooling step of cooling the superabsorbent polymer particles on which the surface crosslinking layer is formed, a water addition step of adding water to the superabsorbent polymer particles on which the surface crosslinking layer is formed, and a post-treatment step of introducing an additive into the superabsorbent polymer particles on which the surface crosslinking layer is formed. In this case, the cooling step, the water addition step, and the post-treatment step may be performed sequentially or simultaneously.
[0327] In the water addition step, water or brine can be used, and the amount of residue produced can be controlled by using water or brine. The amount of water to be used can be appropriately adjusted with consideration of the desired moisture content of the final product. For example, based on absorbent polymers, water can be used in amounts of 0.1% to 10% by weight, 0.5% to 8% by weight, or 1% to 5% by weight, but is not limited thereto.
[0328] In addition, an aging step can be performed after the water addition step.
[0329] If brine is used in the water addition step, the absorption rate of the solution is relatively reduced due to the conductivity of the brine. This allows the brine to diffuse evenly during the aging step, thereby enabling uniform absorption of the absorbent polymer. Common methods can be used in the aging step without particular limitations. For example, the aging step can be carried out using a rotary stirrer at 100°C or lower, 80°C or lower, or 50°C or lower for 10 minutes to 1 hour.
[0330] The additives introduced in the post-processing step may be surfactants, inorganic salts, permeability enhancers, anti-caking agents, flowability enhancers, antioxidants, etc., but this disclosure is not limited to these.
[0331] By selectively performing cooling, water addition, and post-treatment steps, the water content of the final superabsorbent polymer can be increased by controlling the generation of residues, and high-quality superabsorbent polymer products can be prepared.
[0332] In the following, the effects and functions of this disclosure will be described in more detail through specific aspects thereof. However, these aspects are presented only as embodiments of the technical features of this disclosure, and the scope of this disclosure is not limited thereto.
[0333] <Example>
[0334] Example 1
[0335] (Step 1: Polymer preparation steps)
[0336] In a 5 L glass container equipped with a stirrer and thermometer, 1500 g of acrylic acid, 5.25 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3404 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 30.0 g of 0.3% aqueous hydrogen peroxide solution, 15.0 g of 1% aqueous ascorbic acid solution, and 45.0 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 22.5 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0337] (Steps 2 to 3: Micronization and neutralization steps)
[0338] Add 100 g of 0.45 wt% glyceryl monolaurate (GML) aqueous solution to 5,000 g of the polymer obtained in step 1 above. Then, use a high-speed rotary shredder (F-150 / KarlSchnell Co.) installed inside a cylindrical shredder to push the mixture at 2,000 rpm into a porous plate with multiple 10 mm pores for micronization.
[0339] Subsequently, the recovered hydrogel polymer was fed three times at 250 rpm into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer for further pulverization. For each stage of the screw extruder, 1138 g of 50% NaOH aqueous solution (step 3: neutralization step) was introduced to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 162 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0340] (Step 4: Drying step)
[0341] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0342] (Step 5: Crushing and Grading)
[0343] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0344] (Surface crosslinking step)
[0345] Next, every 100 g of base polymer powder was sprayed with an aqueous solution of a surface crosslinking agent containing 4 g of water, 6 g of methanol, 0.15 g of ethylene glycol diglycidyl ether (EJ-1030S), and 0.2 g of aluminum sulfate, and stirred at room temperature to mix the solution so that it was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor for a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 140°C for 40 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0346] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0347] Example 2
[0348] (Step 1: Polymer preparation steps)
[0349] In a 5 L glass container equipped with a stirrer and thermometer, 1500 g of acrylic acid, 4.5 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3402 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 30.0 g of 0.3% aqueous hydrogen peroxide solution, 15.0 g of 1% aqueous ascorbic acid solution, and 45.0 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 22.5 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0350] (Steps 2 to 3: Micronization and neutralization steps)
[0351] Add 50 g of 0.45% by weight glyceryl monolaurate (GML) aqueous solution to 5,000 g of the polymer obtained in step 1 above. Then, use a high-speed rotary shredder (F-150 / KarlSchnell Co.) installed inside a cylindrical shredder to push the mixture at 2,000 rpm into a porous plate with multiple 10 mm pores for micronization.
[0352] Subsequently, the recovered hydrogel polymer was fed three times at 250 rpm into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer for further pulverization. For each stage of the screw extruder, 1396 g of 50% NaOH aqueous solution (step 3: neutralization step) was introduced to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 162 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0353] (Step 4: Drying step)
[0354] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0355] (Step 5: Crushing and Grading)
[0356] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0357] (Surface crosslinking step)
[0358] Next, every 100 g of base polymer powder was sprayed with an aqueous solution of a surface crosslinking agent containing 3.5 g water, 6 g methanol, 0.07 g ethylene glycol diglycidyl ether (EJ-1030S), and 0.2 g aluminum sulfate, and stirred at room temperature to mix the solution so that it was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor for a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 140°C for 40 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0359] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0360] Example 3
[0361] (Step 1: Polymer preparation steps)
[0362] In a 5 L glass container equipped with a stirrer and thermometer, 1500 g of acrylic acid, 3.75 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3400 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 30.0 g of 0.3% aqueous hydrogen peroxide solution, 15.0 g of 1% aqueous ascorbic acid solution, and 45.0 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 22.5 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0363] (Steps 2 to 3: Micronization and neutralization steps)
[0364] Add 100 g of 0.45 wt% glyceryl monolaurate (GML) aqueous solution to 5,000 g of the polymer obtained in step 1 above. Then, use a high-speed rotary shredder (F-150 / KarlSchnell Co.) installed inside a cylindrical shredder to push the mixture at 2,000 rpm into a porous plate with multiple 10 mm pores for micronization.
[0365] Subsequently, the recovered hydrogel polymer was fed three times at 250 rpm into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer for further pulverization. For each stage of the screw extruder, 1383 g of 50% NaOH aqueous solution (step 3: neutralization step) was introduced to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 162 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0366] (Step 4: Drying step)
[0367] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0368] (Step 5: Crushing and Grading)
[0369] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0370] (Surface crosslinking step)
[0371] Next, every 100 g of base polymer powder was sprayed with an aqueous solution of a surface crosslinking agent containing 4 g of water, 6 g of methanol, 0.07 g of ethylene glycol diglycidyl ether (EJ-1030S), and 0.2 g of aluminum sulfate, and stirred at room temperature to mix the solution so that it was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor for a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 140°C for 40 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0372] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0373] Example 4
[0374] (Step 1: Polymer preparation steps)
[0375] In a 5 L glass container equipped with a stirrer and thermometer, 1400 g of acrylic acid, 4.9 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3512 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 28.0 g of 0.3% aqueous hydrogen peroxide solution, 14.0 g of 1% aqueous ascorbic acid solution, and 42.0 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 21.0 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0376] (Steps 2 to 3: Micronization and neutralization steps)
[0377] Add 279 g of 0.45 wt% glyceryl monolaurate (GML) aqueous solution to 5,000 g of the polymer obtained in step 1 above. Then, the mixture is fed at 2,000 rpm into a porous plate with multiple 10 mm pores using a high-speed rotary shredder (F-150 / KarlSchnell Co.) installed inside a cylindrical shredder for micronization.
[0378] Subsequently, the recovered hydrogel polymer was fed three times at 250 rpm into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer for further pulverization. For each stage of the screw extruder, 1319 g of 50% NaOH aqueous solution (step 3: neutralization step) was introduced to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 149 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0379] (Step 4: Drying step)
[0380] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0381] (Step 5: Crushing and Grading)
[0382] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0383] (Surface crosslinking step)
[0384] Next, every 100 g of base polymer powder was sprayed with an aqueous solution of a surface crosslinking agent containing 5 g water, 6 g methanol, 0.1 g ethylene glycol diglycidyl ether (EJ-1030S), and 0.2 g aluminum sulfate, and stirred at room temperature to mix the solution so that it was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor for a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 140°C for 40 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0385] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0386] Comparative Example 1
[0387] (Step 1: Polymer preparation steps)
[0388] In a 5 L glass container equipped with a stirrer and thermometer, 1500 g of acrylic acid, 5.25 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3404 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 30.0 g of 0.3% aqueous hydrogen peroxide solution, 15.0 g of 1% aqueous ascorbic acid solution, and 45.0 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 22.5 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0389] (Steps 2 to 3: Micronization and neutralization steps)
[0390] The polymer obtained in step 1 above was micronized by using a high-speed rotary shredder (F-150 / Karl Schnell Co.) installed inside a cylindrical shredder, which was pushed at a speed of 2,000 rpm into a porous plate with multiple 10 mm holes.
[0391] Subsequently, the recovered hydrogel polymer was fed three times at 250 rpm into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer for further pulverization. For each stage of the screw extruder, 1161 g of 50% NaOH aqueous solution (step 3: neutralization step) was introduced to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 165 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0392] (Step 4: Drying step)
[0393] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0394] (Step 5: Crushing and Grading)
[0395] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0396] (Surface crosslinking step)
[0397] Next, every 100 g of base polymer powder was sprayed with an aqueous solution of a surface crosslinking agent containing 5.5 g water, 6 g methanol, 0.15 g ethylene glycol diglycidyl ether (EJ-1030S), and 0.3 g aluminum sulfate, and stirred at room temperature to mix the solution so that it was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor for a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 140°C for 40 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0398] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0399] Comparative Example 2
[0400] (Step 1: Polymer preparation steps)
[0401] In a 5 L glass container equipped with a stirrer and thermometer, 1500 g of acrylic acid, 5.25 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3404 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 30.0 g of 0.3% aqueous hydrogen peroxide solution, 15.0 g of 1% aqueous ascorbic acid solution, and 45.0 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 22.5 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0402] (Steps 2 to 3: Micronization and neutralization steps)
[0403] Add 597 g of 0.45 wt% glyceryl monolaurate (GML) aqueous solution to 5,000 g of the polymer obtained in step 1 above. Then, the mixture is fed at 2,000 rpm into a porous plate with multiple 10 mm pores using a high-speed rotary shredder (F-150 / KarlSchnell Co.) installed inside a cylindrical shredder for micronization.
[0404] Subsequently, the recovered hydrogel polymer was fed three times at 250 rpm into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer for further pulverization. For each stage of the screw extruder, 1037 g of 50% NaOH aqueous solution (step 3: neutralization step) was introduced to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 150 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0405] (Step 4: Drying step)
[0406] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0407] (Step 5: Crushing and Grading)
[0408] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0409] (Surface crosslinking step)
[0410] Next, every 100 g of base polymer powder was sprayed with an aqueous solution of a surface crosslinking agent containing 5.5 g of water, 5 g of methanol, and 0.07 g of ethylene glycol diglycidyl ether (EJ-1030S), and stirred at room temperature to mix such that the surface crosslinking solution was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor to carry out a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 140°C for 40 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0411] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0412] Comparative Example 3
[0413] (Step 1: Polymer preparation steps)
[0414] In a 5 L glass container equipped with a stirrer and thermometer, 1500 g of acrylic acid, 3.75 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3400 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 30.0 g of 0.3% aqueous hydrogen peroxide solution, 15.0 g of 1% aqueous ascorbic acid solution, and 45.0 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 22.5 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0415] (Steps 2 to 3: Micronization and neutralization steps)
[0416] Add 100 g of 0.45 wt% glyceryl monolaurate (GML) aqueous solution to 5,000 g of the polymer obtained in step 1 above. Then, perform an additional pulverization process by feeding the hydrogel polymer three times into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer at a speed of 250 rpm. For each stage of the screw extruder, introduce 1383 g of 50% NaOH aqueous solution (step 3: neutralization step) to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 162 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0417] (Step 4: Drying step)
[0418] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0419] (Step 5: Crushing and Grading)
[0420] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0421] (Surface crosslinking step)
[0422] Next, every 100 g of base polymer powder was sprayed with an aqueous solution of a surface crosslinking agent containing 3.5 g of water, 5 g of methanol, and 0.12 g of ethylene glycol diglycidyl ether (EJ-1030S), and stirred at room temperature to mix the solution so that it was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor for a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 140°C for 40 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0423] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0424] Comparative Example 4
[0425] (Step 1: Polymer preparation steps)
[0426] In a 5 L glass container equipped with a stirrer and thermometer, 1500 g of acrylic acid, 3.0 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3399 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 30.0 g of 0.3% aqueous hydrogen peroxide solution, 15.0 g of 1% aqueous ascorbic acid solution, and 45.0 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 22.5 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0427] (Steps 2 to 3: Micronization and neutralization steps)
[0428] Add 100 g of 0.45 wt% glyceryl monolaurate (GML) aqueous solution to 5,000 g of the polymer obtained in step 1 above. Then, perform an additional pulverization process by feeding the hydrogel polymer three times into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer at a speed of 250 rpm. For each stage of the screw extruder, introduce 1140 g of 50% NaOH aqueous solution (step 3: neutralization step) to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 162 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0429] (Step 4: Drying step)
[0430] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0431] (Step 5: Crushing and Grading)
[0432] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0433] (Surface crosslinking step)
[0434] Next, an aqueous solution of a surface crosslinking agent containing 5 g water, 6 g methanol, 0.15 g ethylene carbonate, and 0.38 g aluminum sulfate was sprayed onto every 100 g of base polymer powder, and the mixture was stirred at room temperature to ensure that the surface crosslinking solution was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor to undergo a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 185°C for 50 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0435] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0436] Comparative Example 5
[0437] (Step 1: Polymer preparation steps)
[0438] In a 5 L glass container equipped with a stirrer and thermometer, 1450 g of acrylic acid, 3.63 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3454 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 29.0 g of 0.3% aqueous hydrogen peroxide solution, 14.5 g of 1% aqueous ascorbic acid solution, and 43.5 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 21.75 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0439] (Steps 2 to 3: Micronization and neutralization steps)
[0440] Add 96 g of 0.45 wt% glyceryl monolaurate (GML) aqueous solution to 5,000 g of the polymer obtained in step 1 above. Then, perform an additional pulverization process by feeding the hydrogel polymer three times into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer at a speed of 250 rpm. For each stage of the screw extruder, introduce 1417 g of 50% NaOH aqueous solution (step 3: neutralization step) to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 159 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0441] (Step 4: Drying step)
[0442] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0443] (Step 5: Crushing and Grading)
[0444] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0445] (Surface crosslinking step)
[0446] Next, an aqueous solution of a surface crosslinking agent containing 3.5 g water, 5 g methanol, and 0.1 g ethylene glycol diglycidyl ether (EJ-1030S) was sprayed onto every 100 g of base polymer powder, and stirred at room temperature to mix the solution so that it was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor for a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 140°C for 40 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0447] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0448] Comparative Example 6
[0449] (Step 1: Polymer preparation steps)
[0450] In a 5 L glass container equipped with a stirrer and thermometer, 1400 g of acrylic acid, 2.8 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3506 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 28.0 g of 0.3% aqueous hydrogen peroxide solution, 14.0 g of 1% aqueous ascorbic acid solution, and 42.0 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 21.0 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0451] (Steps 2 to 3: Micronization and neutralization steps)
[0452] Add 279 g of 0.45 wt% glyceryl monolaurate (GML) aqueous solution to 5,000 g of the polymer obtained in step 1 above. Then, perform an additional pulverization process by feeding the hydrogel polymer three times into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer at a speed of 250 rpm. For each stage of the screw extruder, introduce 1027 g of 50% NaOH aqueous solution (step 3: neutralization step) to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 149 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0453] (Step 4: Drying step)
[0454] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0455] (Step 5: Crushing and Grading)
[0456] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0457] (Surface crosslinking step)
[0458] Next, an aqueous solution of a surface crosslinking agent containing 3.5 g water, 5 g methanol, 0.15 g ethylene carbonate, and 0.2 g aluminum sulfate was sprayed onto every 100 g of base polymer powder, and the mixture was stirred at room temperature to ensure that the surface crosslinking solution was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor to undergo a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 185°C for 50 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0459] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0460] Comparative Example 7
[0461] (Step 1: Polymer preparation steps)
[0462] In a 5 L glass container equipped with a stirrer and thermometer, 1400 g of acrylic acid, 2.8 g of pentaerythritol triallyl ether (PETTAE) as an internal crosslinking agent, and 3506 g of water were stirred and mixed, and then reacted while maintaining the temperature at 5 °C. Nitrogen gas was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to purge the mixture under nitrogen conditions. Next, 28.0 g of 0.3% aqueous hydrogen peroxide solution, 14.0 g of 1% aqueous ascorbic acid solution, and 42.0 g of 2% aqueous 2,2'-azobis-(2-amidinylpropane)dihydrochloric acid solution as polymerization initiators, and simultaneously 21.0 g of 0.01% aqueous ferrous sulfate solution as a reducing agent were added to initiate polymerization. After the temperature of the mixture reached 85 °C, the mixture was polymerized at 90 ± 2 °C for approximately 6 hours to obtain the polymer.
[0463] (Steps 2 to 3: Micronization and neutralization steps)
[0464] Add 279 g of 0.45 wt% glyceryl monolaurate (GML) aqueous solution to 5,000 g of the polymer obtained in step 1 above. Then, perform an additional pulverization process by feeding the hydrogel polymer three times into a porous plate with multiple 10 mm holes using a screw extruder installed inside a cylindrical pulverizer at a speed of 250 rpm. For each stage of the screw extruder, introduce 1027 g of 50% NaOH aqueous solution (step 3: neutralization step) to neutralize a portion of the acidic groups in the polymer, followed by the introduction of 100 g of fine powder (another additive introduction step) and 149 g of 10% Na2SO4 aqueous solution (another additive introduction step) to prepare aqueous superabsorbent polymer particles (=micronized and neutralized polymer).
[0465] (Step 4: Drying step)
[0466] 1,000 g of water-containing superabsorbent polymer particles were introduced into a ventilated belt dryer comprising a porous plate capable of vertically shifting air volume. To achieve a moisture content of approximately 10% in the dried superabsorbent polymer, hot air at 200°C and hot air at 100°C were sequentially circulated from top to bottom for 5 minutes and 10 minutes, respectively, followed by a further circulation of hot air at 100°C from bottom to top for 15 minutes to uniformly dry the polymer.
[0467] (Step 5: Crushing and Grading)
[0468] Use a grinder (GRAN-U-LIZER) TM The dried body (MPE) is pulverized and then graded using a standard mesh sieve according to ASTM standards to obtain a base polymer powder with a size ranging from 150 μm to 850 μm.
[0469] (Surface crosslinking step)
[0470] Next, every 100 g of base polymer powder was sprayed with an aqueous solution of a surface crosslinking agent containing 4.5 g water, 5 g methanol, 0.1 g ethylene glycol diglycidyl ether (EJ-1030S), and 0.4 g aluminum sulfate, and stirred at room temperature to mix the solution so that it was uniformly distributed on the superabsorbent polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor for a surface crosslinking reaction. In the aforementioned surface crosslinking reactor, the base polymer powder underwent a surface crosslinking reaction at approximately 140°C for 40 minutes to obtain a surface-crosslinked superabsorbent polymer.
[0471] Following the surface crosslinking step described above, the surface-crosslinked superabsorbent polymers are graded using a standard mesh sieve according to ASTM standards to prepare superabsorbent polymers with particle sizes ranging from 150 μm to 850 μm.
[0472] <Experimental Example>
[0473] The physical properties of the superabsorbent polymers prepared in the examples and comparative examples were evaluated using the following methods, and the results are shown in Table 1 below.
[0474] Unless otherwise stated, all assessments of the following physical properties were conducted at constant temperature and humidity (23±1℃, 50±10% relative humidity), and physiological saline or brine refers to a 0.9% by weight aqueous solution of sodium chloride (NaCl).
[0475] The sample to be measured was placed under constant temperature and humidity conditions for 24 hours, and its various physical properties were evaluated.
[0476] In addition, unless otherwise specified, the physical properties of the final superabsorbent polymer are evaluated for polymers with particle sizes of 300 μm to 425 μm using ASTM standard sieve classification.
[0477] (1) Measurement of the shape of superabsorbent polymer particles
[0478] For the superabsorbent polymers of the examples and comparative examples, the aspect ratio (A / R), convexity, and roundness were measured using a morphologi 4 from Malvern Panalytical Co., Ltd. in the following manner.
[0479] 1) Sample preparation: Prepare 1 g of superabsorbent polymer particles to be measured.
[0480] To measure the aspect ratio, convexity, and roundness of particles with a diameter of 100 μm to 600 μm, the superabsorbent polymer was fractionated for 10 minutes at an amplitude of 1.0 using a Retsch classifier, separating it into individual particles with a diameter of 100 μm to 600 μm without damaging the particles, to prepare a 1 g sample. The sample dispersion unit settings at this time were as follows: Figure 1 As shown.
[0481] 2) Image Acquisition: Place the prepared sample on the stage of the instrument, and then scan at a magnification of 2.5 to obtain images of each particle. At this time, the illumination settings and optics selection settings are as follows: Figure 2 and Figure 3 As shown.
[0482] 3) Image Processing: For the acquired images, which are captured as 2D images of 3D particles, the parameter values of each particle are measured, such as the equivalent circle (CE) diameter, shortest diameter, longest diameter, actual particle circumference, convex hull circumference, etc. At this time, the scanning area settings are as follows: Figure 4 As shown, the measurements were taken without setting a filter value for the particles.
[0483] 4) Based on the data from the analysis of each particle, a distribution map of the parameters of all particles contained in the sample is obtained.
[0484] [Table 1]
[0485]
[0486] (2) Centrifuge retention capacity (CRC, g / g)
[0487] The centrifugal retention capacity of the superabsorbent polymers of the Examples and Comparative Examples under no-load conditions was measured according to the European Disposable Products and Nonwovens Association (EDANA) standard EDANA WSP 241.3.
[0488] In addition, the centrifugal retention capacity of the final superabsorbent polymer was measured for polymers with particle sizes ranging from 300 μm to 425 μm using ASTM standard sieve classification.
[0489] As described in EDANA WSP 241.0, measurements were performed at a temperature of 23±2°C and a relative humidity of 45±15%.
[0490] Specifically, the superabsorbent polymer W0 (g) (approximately 0.2 g) obtained by each of the Examples and Comparative Examples was uniformly placed into a nonwoven fabric bag and sealed, then immersed in physiological saline (0.9% by weight) at room temperature. After 30 minutes, the bag was drained for 3 minutes using a centrifuge at 250 G, and the weight of the bag W2 (g) was measured. Furthermore, the same procedure was performed without the polymer, and the weight W1 (g) was then measured.
[0491] CRC (g / g) is calculated using the obtained weights according to Equation 5 below.
[0492] [Equation 5]
[0493]
[0494] Repeat the above measurement 5 times and obtain the mean and standard deviation.
[0495] (3) Vortex time
[0496] The vortex time of the superabsorbent polymers in the examples and comparative examples was measured using the following method.
[0497] In addition, the vortex time of the final superabsorbent polymer was measured for polymers with particle sizes ranging from 300 μm to 425 μm using ASTM standard sieve classification.
[0498] 1) First, use a 100 mL graduated cylinder to add 50 mL of 0.9% saline solution to a 100 mL beaker with a flat bottom.
[0499] 2) Next, place the beaker in the center of the magnetic stirrer and place the round magnetic rod (30 mm in diameter) inside the beaker.
[0500] 3) After that, operate the stirrer so that the magnetic rod stirs at 600 rpm and the bottom of the vortex generated by stirring comes into contact with the top of the magnetic rod.
[0501] 4) After confirming that the temperature of the brine in the beaker reaches 24.0℃, introduce 2±0.01 g of superabsorbent polymer sample into it, and simultaneously operate a stopwatch to measure the time until the vortex disappears and the surface of the liquid becomes completely horizontal. Set this as the vortex time.
[0502] (4) Absorption rate in water with a conductivity of 110 μS / cm for 1 minute (110 μS / cm 1 minute absorption rate)
[0503] The absorption rate (g / g) of the final superabsorbent polymer in water with a conductivity of 110 μS / cm was measured for polymers with particle sizes ranging from 300 μm to 425 μm using ASTM standard sieve classification.
[0504] 1.0 g (W3) of each of the superabsorbent polymers from the examples and comparative examples was placed in a nonwoven fabric bag (18 cm × 28 cm) and immersed in 1000 mL of water with a conductivity of 110 μS / cm for 1 minute at 24°C. After 1 minute, the bag was removed from the water with a conductivity of 110 μS / cm and then suspended and left to stand for 1 minute. The weight W5 of the encapsulated material was then measured. The same procedure was performed without the superabsorbent polymer, and the weight W4 was measured at this time. Using the weights obtained as described above, the absorption rate (g / g) in water with a conductivity of 110 μS / cm for 1 minute was calculated according to Equation 6 below.
[0505] [Equation 6]
[0506] The absorption rate in water with a conductivity of 110 μS / cm for 1 minute is calculated as: {[W5(g) – W4(g) – W3(g)] / W3(g)}
[0507] [Table 2]
[0508]
[0509] (5) Calculation of factor values
[0510] Substitute the centrifugation retention capacity (CRC), aspect ratio (A / R), convexity, and roundness obtained above into Equations 1 and 2 below to calculate the factor values F1 and F2.
[0511] [Equation 1]
[0512] F1 = K1×[{(A 0.1 ×C×D 0.5 )} / (B 0.3 )]
[0513] [Equation 2]
[0514] F2 = K2×[(B 0.2 ) / {(A 0.1 ×C×D 0.5 )}]
[0515] In equations 1 and 2 above,
[0516] i) K1 and K2 are correction constants of 0.5 and 0.8, respectively.
[0517] ii) A represents the centrifugation retention capacity (CRC) of particles with diameters ranging from 300 μm to 425 μm, measured according to the WSP 241.3 method of the EDANA method, and
[0518] iii) B, C and D are the average aspect ratio (A / R), average convexity and average roundness of particles with a diameter of 100 μm to 600 μm, respectively.
[0519] [Table 3]
[0520]
[0521] Figure 5 A graph showing the correlation between factor value F1 and vortex time; and Figure 6 A graph showing the correlation between factor value F2 and 1-minute absorption rate in water with a conductivity of 110 μS / cm is presented. See Table 3 above. Figure 5 and Figure 6It can be determined that the factor value F1 in Equation 1 above is proportional to the vortex time, and the factor value F2 in Equation 2 above is proportional to the absorption rate in 1 minute in water with a conductivity of 110 μS / cm.
[0522] In particular, in Examples 1 to 4, where the F1 value is between 0.55 and 0.65 and the F2 value is between 0.65 and 0.75, it can be seen that the absorption rate is high and the absorption performance is excellent.
[0523] That is, if the factor values F1 and F2, which represent the relationship between centrifugal retention capacity (CRC), aspect ratio (A / R), convexity and roundness, are adjusted to predetermined values, a superabsorbent polymer with an excellent balance of physical properties can be achieved by improving the absorption rate and absorption performance.
[0524] Industrial applicability
[0525] This invention is applicable to superabsorbent polymers.
Claims
1. A superabsorbent polymer based on polyacrylic acid (salt), wherein: The F1 calculated using Equation 1 is between 0.55 and 0.65, and The F² calculated using Equation 2 is between 0.65 and 0.
75. [Equation 1] F1 = K1(0.5)×[{(A(CRC) 0.1 ×C (convexity) ×D (circularity) 0.5 )} / (B(Aspect Ratio) 0.3 )] [Equation 2] F2 = K2×[(B 0.2 ) / {(A 0.1 ×C×D 0.5 )}] In equations 1 and 2: i) K1 and K2 are correction constants of 0.5 and 0.8, respectively. ii) A is the centrifugal retention capacity (CRC) of particles with a diameter of 300 μm to 425 μm, as measured according to WSP 241.3 of the European Disposable and Nonwovens Association (EDANA). iii) B, C and D are the average aspect ratio (A / R), average convexity and average roundness of particles with a diameter of 100 μm to 600 μm, respectively.
2. The superabsorbent polymer according to claim 1, wherein the F1 is 0.57 to 0.
64.
3. The superabsorbent polymer according to claim 1, wherein the F2 is 0.65 to 0.
72.
4. The superabsorbent polymer according to claim 1, wherein the centrifugation retention capacity (CRC) of the particles with a particle size of 300 μm to 425 μm is 30 g / g or greater.
5. The superabsorbent polymer according to claim 1, wherein the average aspect ratio (A / R) of the particles with a particle size of 100 μm to 600 μm is 0.65 to 0.
85.
6. The superabsorbent polymer of claim 1, wherein the average convexity of the particles with a particle size of 100 μm to 600 μm is 0.80 to 0.
94.
7. The superabsorbent polymer according to claim 1, wherein the average sphericity of the particles with a particle size of 100 μm to 600 μm is 0.70 to 0.
90.
8. The superabsorbent polymer of claim 1, wherein the vortex time of the particles with a particle size of 300 μm to 425 μm is 40 seconds or less, wherein the vortex time is measured at 24.0°C according to the vortex measurement method.
9. The superabsorbent polymer according to claim 1, wherein when 1 g of the particles with a particle size of 300 μm to 425 μm is swollen with water with a conductivity of 110 μS / cm for 1 minute, the free swelling capacity of the superabsorbent polymer is 120 g or greater.
Citation Information
Patent Citations
Information processing device, information processing method and computer program
KR1020240038728A